VERBA DWITRANSITIF DALAM BAHASA INDONESIA - Listiyorini, Ari (Diksi, 2015)
<img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAegAAAEzCAIAAAB1ywe3AAAgAElEQVR4nOydeTyWWf/HL2uSCmWXpW1IokUr7YuMNpWiRRmVjIxqpqSUXbJv2SVZC0kiLcoSsiaUyJ59X27cuO/r98f39ZzX9VA9zUzPzGN+5/3HvMx1n+tcZ/mez/me7znXFUFiMBgMZkJB/N0FwGAwGMzvAws3BoPBTDCwcGMwGMwEAws3BoPBTDCwcGMwGMwEAws3BoPBTDCwcGMwGMwEAws3BoPBTDCwcGMwGMwEAws3BoPBTDCwcGMwGMwEAws3BoPBTDCwcGMwGMwEAws3BoPBTDCwcGMwGMwEAws3BoPBTDCwcGMwGMwEAws3BoPBTDCwcGMwGMwEAws3BoPBTDD+s3Azmcy/oBxjnvgtD/16mv+Ywzc+5ffylzUXkwL1yreX5LMJ/vru/ha+0R7Gt8Z3rOPvbdtvfMofMPXvVa+v5PMlo/q9+f+xG/8MzHF8PeWXfvozT/8Dd33p7y/l9k0ed1dXl7e3t7e3961bt27duuXr6xsSElJVVUWS5Lt373799ddffvklICDAzc3NwcHh5s2bQf/Cx8fH3d3dy8vLz88vKCgoOzubRqPFxMScP3/exsYmICAgODjY19fXw8PD09Pz3r17b9++HRwchIf29vb6+vp6enpCVgEBAV5eXjdv3gwJCXn27Flzc/Nni9rd3V1WVvalX8c3Fo1GS0lJcXNzCwgICAoKCgwM9PPz8/LyCg8Pf/36NYPBgMQ0Gi01NRWqFhgYGBwc/OjRo9LS0rt376L6enh4PH36FMoQHx8fGBjo6+vr7u7u7u7u7+8PaW7evPno0aO3b9/evXs3ICDAx8cHWubWrVtBQUG+vr5+fn7e3t75+flv3rxxdnYODAyEG/38/Nzd3T09PaOionJycqDwDAaDwWBQu5bBYDQ2NmZnZ3d2dpIUI2hsbLx7966/v7+fn19YWFhTUxO65fHjx25ubn5+ftHR0dCnJElWV1f7+vq6urqGh4cXFBSUlZW1tLS0tbUlJCS4u7uDGfj5+d2+ffv9+/dlZWURERHe3t4+Pj6opgEBAX5+fn5+flFRUQUFBYmJiXARfnVzc3v27NmLFy9QblBHHx8fHx+fgIAAX1/f6upqak9VVVW5urpS8/fx8QkPD8/KyhodHUXVpyoOXKmqqioqKuru7qZeb29vj42NReUJDAy8devWp0+fvmIwDAajoqLi4cOHDQ0N1Outra3R0dG+vr7QWXFxcS0tLdQEw8PDeXl50NH+/v6BgYGlpaWozCRJpqSkODg4oML4+Ph4eHj4+fk9ePCgvr6eWmwqNTU10dHRdDqdevHt27cBAQFoqPr4+Ny+fTsvL8/b25s6MJ2cnLKzs8dkOzQ0FBMT09fXR21JlKCkpMTHx8fZ2dnLy+vFixfv3r1LT09va2sbU6qurq6MjIyysjKo4Gd1p7m5OTo6Grry1q1bgYGBXl5e0dHRUODAwMCQkJCCggJI3NfXFx8fD9d9fX1dXFzADKCCgYGB3t7efn5+ycnJHR0dqKeoQ2NkZCQ1NRV0xtXVNSgoqKSkBBWmra0tLi7O09MzICAgPDy8uLh4eHiYJMnR0dHCwsLg4GAYNffv3w8PDwc5gkf7+/vD+A0MDAwMDHz8+DEMOmQV8fHxTk5OISEhbW1tTCaztbW1tbX18ePH6enpFRUVFRUVGRkZDx48+PDhA7VxGAxGR0dHQ0MDjUYj/92kqXyTcHd3d1+9enXevHnCwsKioqKysrKOjo5g5VVVVQcPHiQIQkJC4vz5876+vjt27BAXFxcVFRUVFd2wYcOJEyd27949d+7cGTNmHD16dHBw8PHjx8uWLePm5hYWFhYTE1u7du3x48dXrFghLi6+efPmn3/+OS0tjSRJGo1ma2urpKQEWS1YsGDv3r0qKioCAgJLlizR0dF58eLF+KLGxcVt37799u3b31IvJpM5ODiYkpKiqakpLS0tKioqJia2dOlSVVVVRUXFVatWnTp1KjExkSTJwcHB2NhYeXl5UVFRERERSUlJS0vLnJyc3377TVJSEkooLi5uZ2dHkmRfX5+Dg4OkpOTChQv19PROnDixcOFCSCMlJWVvb3/nzh1paekZM2asWLFCQUFBXFxcTExMQEBAQUFBRkaGm5v7l19+iY+P3717N8pcXl5eT09v3759P/zwg7KysoGBARp41H4dGRnx9vZet27dmzdvSMqwaWhoOH/+vLCwsJCQkJSUlJaWVn5+Pvzk4+MzZ86c6dOna2pqlpeX02i08PBwDQ0NFRWVU6dO6ejorFu3btu2bd7e3hUVFUFBQStWrBD9FwcPHnz27Nm+ffugTVatWjV//nz4SVpaet68eby8vPPmzTMzM/P09Fy2bJmQkJCoqKiwsPDGjRvj4uIiIyPXrFkD6WfNmqWgoLB69epVq1bx8vLy8/PfvXsXdRNJkuXl5VpaWtBNoqKic+fOXb58+cKFC1euXKmvr//gwQM05VPvIknS3Nx88+bNmZmZ1F87Ojqsra3nzJkDuYFxoqniS9Zia2srJyd3//596vXm5mYLCwtZWVkRERFRUVEZGRlXV9euri6UoKioaNeuXYKCgvAsNTW1jIwM8AmgkE+fPt2zZ8/cuXNFRUUlJSXXr1+/b9++hQsXysjIaGhoeHt79/T0jKlXT0+PjY2NkpLSmGFfUlJy+fJlRUVFeNbs2bMvXLhQUlJiY2OzZs2aWbNmiYqKCgoKKisrv3z5ktpKw8PDDx8+VFBQuHv37tDQ0Bi7ev78+ZYtWxYvXmxkZHT69Ok1a9Zs3Ljx8OHD7969G9NKqampq1atMjMzGxkZIb8s3JcuXYKhBINu9+7dd+7cMTc3X7RokYiIiLi4+IYNG6Kjo0mSHBgYCAsL27Rpk6io6JIlS65evWpiYoIqKC0traSkpKioOHfuXG1tbUdHR5ihUfnLy8uvXbu2dOlSERERTU3NY8eOSUlJbd682dzcvLGxkSTJlpYWGxsbWVlZYWFhaWnpHTt2JCQkkCTJYDDu3LmjrKwsJCQ0e/ZsIyOja9eurV27FonbvHnzVq5cKSMjw8XFxcvLq6CgkJqaChVMSEjQ1NRUVlbW0tJSVVXdtm2bnp6ejY3NmzdvrK2tt2zZoq6urq6uvnTp0r179+bm5o5pn+vXr+vp6ZWWlpJ/Rrjhturq6j179hAEQRDElClTkpKS0E/JycnTpk1bu3ZtZWUlSZKOjo7c3NyQ8vz588XFxVlZWebm5nx8fAsWLIA8IyIipk+fDmkOHDjw4sWLO3fubNiwAa5s3769rq4OOtjU1HTy5MkEQUhLS/v6+kZERGzZsgWSqaqqjnFtSJL8+eefCYI4ePBge3v7l+wGAYNndHT0/v378+bNg2zXrl0bGhrq4OAwbdo0giAWLFgAJt7a2qqvrw9p2NjYwsPD+/v7c3JyVqxYARfnzJkTGxsLOSclJXFxcWlqaubn5xcWFi5ZsgTSLFu27O3bt4GBgQRB7Nu3Lygo6MSJE6ysrARBCAgImJubu7q6ysjIrFmzpqioKCoqatasWXCjhoZGTk5OSkqKqqoqXNm5c2dZWdmYOnZ1dSkrKxMEcePGDeRjQh1fvHihoqJC/Iv9+/dD61VVVR06dGju3LkuLi6jo6M5OTmSkpJcXFxRUVGlpaXJycm7d++GJq2rq2tsbDxz5gzkMHXqVHd394qKCnl5eXFxcRMTk5CQkNWrV8OvSkpKTk5OR44c4eHhOXbs2Js3b3788Uf4iYODw97evqenp7Gx8bfffoOLkydPNjAwuHPnzoMHD4yNjXl4eC5fvgyDH6DT6QkJCTIyMpBeTk7OxcXF3t6el5eXIIj58+ffvHkTvEVkt0wm88OHD4sWLSIIws/Pb4xVp6eno9yEhYVBsL5iLXQ6fd26dQRBXL58Gbwh1LZ5eXmampqobRcvXvz+/XtkY66urtDFBEFwcXGZm5sjRxUKSafT/fz8hISEwLTAKTE1NYVb+Pj4/Pz8ent70S0kSVZWVi5cuJCTk9PNzQ2cbuQgv379Gg2l+fPnFxUVkSRZX1+/b98+uDht2jQnJ6f+/n5qMKGzs/PQoUMEQezZswcMA9nVmzdvoFu1tbVramrevHljamrKzs6uqKhIdV1JkhwYGLh+/TpBEAoKCiCL4wcgk8lkMBhZWVlqamqoxYKDg3t7eysrKzdv3owuLlmyBPzuzs5OExMTTk5OQ0PD1tbW+vr6bdu2QRppaWlHR0cPDw8FBQWCIFhZWS9evNja2grPysrK2r17NycnJxsb2/79+1++fJmXl3f69Gm49+TJk+B9FhcX79+/Hz1XRUUlPT2dJMmSkhITE5PJkyevWrXq4cOH7969s7KyAuHi4uLS0dG5ffu2n5/f+fPn586dSxBEREQESZKvXr2Sl5eHIZaTkxMREQFjdt26de/evcvJyQGDJAhixowZaKahDuHFixcTBAHe55eiJb8jxp2WliYpKQmPdHBwoNPp8FNISMjs2bPj4+MhWWJiori4OCS7c+cOjUYrLCysrKy8cuXKxo0b4ZaWlhYpKSlIY2RkBEVPSkqaOXMmQRD8/Pz+/v6Q8uXLl9LS0gRBLFy4EDzxxMTEqVOnEgQhLi6ekpJCLWpJScny5csJgpCSkrp3795n7YZaL9QotbW1yBR27doFSx5DQ0OYgbZs2QKzX3Z2toSEBEEQnJyczs7OMM7d3Nyg2PPnz4+LiyNJcmRkJCIiQkJCIjk5GZ6FbFRfX58kyfDw8OXLl8OKOyoqCmaI1atXl5eXkyTp7++vp6fX1NRUXl4OKjxlyhRbW1tYez569AjmGGFh4Tt37lBrxGAwkpKSwLDk5eXRYhMYHBy8ceMGss5JkyZdunQJTPzWrVsaGhovX77s7e01MTEhCEJERATd3tDQsHTp0n379oGVBwQEQA4SEhIpKSm9vb2mpqYuLi4gHzo6OvCrgYEBSZKfPn3S1NS8dOlSZ2fn2bNnJ02aRBCEqKjokydPIPOwsDBILyIi8vjxY5IkX79+3dXVtWLFChMTkzFxgIaGBnV1dUi/Y8cOWBpfunQJtHvWrFngo1G72NLSkoeHhyCIvXv3gmOBOr2tre348eMsLCwEQaipqYGv8BVrefz4sbCwMEEQS5cuffXqFfXX4eFhLy8vNjY2KBsnJ2dsbCz0V0NDg4aGBmp2ISEhMBKqEVK7VUBAwN3dnSTJ9vZ2RUVFuGvbtm1ggXBLX19fUFAQBwcHQRArV64EQ0JZ1dXVHThwAG5cu3YtKuHZs2fBB1q8eDF1uQZ3lZSUwEATERHJycmh1s7LywsM5vTp0wMDA3BRX19/5cqVkBK0GDIB54Cbm9vd3R1iDuNbkiTJzs7O8+fPQ+NzcnKCC0KS5KlTp1BbsbKyHjhwAGas8PBwISEhtMgG/4wgCFlZ2WfPnpEk+fjxYzTzOTo69vX19fT0HDlyBJKtXLmyoqIC7m1paUENa2xsDLOUg4MDQUFFRQUGY1pa2qxZs06cOAHFeP78uaysLEEQgoKCgYGBJEk2NzePjo6GhoaysLDAFSMjI4IgeHh4bG1t0RPV1dW3bt0KSzotLS14iqqqKgpOIqWKjo4WEREhCOLIkSOoZ8c34+87VXL06FFOTk6CILZv3w6W1NTUpKmpuWLFiv7+fnjGgwcPxMTEoGSxsbGvXr3avHlzREREdXV1SEgIdHBfX9/s2bMhzZkzZ2Bd+ezZMzAdXl5eR0dHSBkRESEqKgpKBKvde/fu8fPzEwQxc+ZMiGMgjI2N0eDR1dWFbL9lr6CiogJN9RoaGtBeyL9jYWE5d+4cSZLd3d2//vorJFNUVIRuSEtLW7ZsGVjML7/8Am2ipaW1ceNG8PpJkkRusq6ubm9v75s3b8LCwkiSHB0dvX37Ngi3iIgILLVqa2tfv37d29tbVFS0atUqGAZWVlYwT6Smpi5cuBDkDzJBtLe379mzB1qAnZ09NDQUxehJkuzp6bG0tJw5cya4A1DgGzdujIyMhIaGrlq1KjIysqmpCfwyVlbWNWvWPHz4EOQsJCTE19cX/MSbN2/C7bNmzUpMTIRNAkg2MjKyd+9e+PXEiRMkSfb397948eLFixddXV0GBgYg3FJSUmhKCw4OhvSioqLJyckNDQ1Llix59eqVk5MTLHSoVFdXo5bcvn17bW0tSZKFhYUwvREEoaWlRQ2YdHd3r1+/Hn7i5ub29vamSlVfX5+dnR3I35YtWz5+/PgVC+np6aF6iA4ODtQg9cDAgLOz8+TJk2fNmgUDZP/+/WAeoaGh8vLyEhIS8CBBQcF79+5R+wWIj48Hr01MTCwkJIQkyaGhIVR4DQ0NavGKi4vRGo6LiysuLo4al6ipqUH+47p169BdPj4+M2bMIAhi0aJFaFEP9PX1Xbp0CdXO1NSU6gYiUZs9e7aZmVleXh6dTv/48aO7uzta84F23759G2WiqKgITvdnqampQSsATk7Ot2/fwnUdHR1hYWG00JwxY4aLi0t/f/+dO3eEhIRgviEp+i4mJgZrqZaWFtRc8+fPLykpSUhIAEeTk5PzzJkz1M769ddfYQ7j4eGByd7S0pKLiws8MIIgODg4Tpw40dbW9vz5czExscuXL4NwJyUl/fDDD2BOV65cqaur09XVffr0aV9fn5GREUwhqF7KyspPnz4FFXrw4IGJiQkME9Q7mzZtos7HJEl2dHTs2rULhrCoqGhMTAz554WbyWQmJCSAyzl16lR/f3+SJENCQsTFxS0tLVEaqnC7u7s7OjpKSEh4enpSy9fT04OE+9SpU3V1dT09Pcg+pKWls7KySJIcHR21sbEBF3LevHmhoaGlpaUnT56EFt+zZw+aqMEUlJWVeXh4oEvmzp0L1f4WkHCzsbH9+uuv4HFXVlYimVBTU4M448OHD7m4uODikydPmEymj4+PgIAAXFm+fPnHjx9fvXolJSXl4OCA3BOUz759+9B2E0mSdDr99u3bKGpE9cVIkiwsLFy5ciVBEJMnTzYzMxseHu7v77eysoLhN3/+fCR/0FbJyck8PDwsLCzgyGhpadXU1KA27+3tvXbtmoqKytOnT1GIYN68eS9fvrx9+/a+fftgZzUgIICdnR1+nT59+pEjR549e0aN2FKFOz4+nmpV7e3tyCMG4UbQaLRTp06BcCsqKsLiifx34Q4ICPD09BQWFs7IyPhsN40RbqhdV1cX7LIQBLFmzRoU82Uymffu3RMREeHg4ICRcPToUWoQYGhoyNfXF3T268LNZDLT0tIEBASmTZsG6Xft2kUNLkO/iImJ2dnZgZ/Bzs5+//79wcHB3bt3r169+tq1a1OmTCG+Qbi5ublPnz797t27O3fuwEpCUlIyJCQERY2YTGZ4eDg3Nzc8iI2NbefOndSYIVW4ly5d+uHDh/Ly8rKyMj8/P1gxUIUbmuLVq1d8fHyioqJgOWJiYtQlBSoJsHDhQldXV3BIqZmUl5cfOHBgypQp0EQ8PDxPnjyhTm9UYKqDCBJVuPfv3797925XV1e0ahcUFAwNDQ0LCxMXF0elQsK9cuVK2K3p6OjQ09OD2ZEgiNTU1IsXL8LfQkJC3t7e6NHDw8P+/v5Ioy0tLZlM5pUrV+bOnXvp0qUFCxbAdS4uLh8fn8ePH0tLSwcFBcG9ycnJ4HFPnTr17NmzYWFhYmJiVA+DyWSamJgg91FKSsrU1LSgoKCurq62thZWkJ8VbpIkGQzGo0ePkJgQBGFsbEwNylH5fR53Z2cnSAlBECdPniwrK9PR0VmyZAlaZjKZzPj4eCTcioqKEhISgoKCYxb1VOFevny5hYWFhYUFRHb4+flPnz4NpkCn0y0sLEDXpkyZoqysvGLFCuibRYsWwf4bwtraWllZ+dKlSxs3biQIgoODw8TE5BvrhYQbYiCosfT09MbYR1VVFVK9U6dOFRUV7dy5k5+fHyybn5/fxMTE2tp69uzZaGlGUoT7xIkTVJdweHg4JCQEKjh58mTYOUAg4WZjY1NVVY2NjbW3t5eTk2NhYREUFLx27Ro1pNva2nr48GF5efkdO3ZAYWbOnAnbaCAT7e3t+vr68vLy7e3tHh4eaLbYvXv3sWPHfv31V5gFKysrtbS0YPIDpk2bZmhoiKpDFe6HDx9ShbuwsBDFuD8r3DCkFRQUxgs3Dw/PqlWr+Pj42NnZ8/LyPttNnxVu8l+LU9AptMxvbm7esmXLpk2bdu/eDYNBTk6OukSj0WguLi5f97iRH6Snp7dkyZLffvsN5JWXlxf8YhT6++mnn2bPnp2RkSEnJweFuXr16v379xUUFC5cuIAiQv9RuNnY2GRkZDZu3AgaShDElStXYDkLd3369Onw4cMbNmzw8/ODUB47O/urV6/QLhZVuPn5+Xfu3Llnz54dO3YoKSmBzzHG4+7r67t8+fKCBQtu3boFbhlBEAEBAUhzOzs7r127ButChIqKyoMHD2A6gYJ5e3vPnz//5MmTyGi1tbXHHzsBYP33WeHetGlTWVmZi4sLeqKsrOylS5fExMTQDjNVuCGmNzw8HBQUBGExgiDCwsK0tbVRm9+8eRM9msFgxMbGQlyFIAg9Pb3R0VEzM7NFixYVFhbeuXMHIrHQUObm5iC+oAlxcXHgxU+ePHnZsmVLlizh5+fPzc2lzk/Z2dmqqqqo+wiCADeutrYWGupLwk2j0QwMDOTk5GRkZGCal5eXh/jheH73Czjnz5+H7l+9erWBgYGsrKyuri76lclkxsbGIl9g+fLl0tLSixYtgkUEtduQcE+fPp2Hhwd14fnz55EWDA4OGhkZgYgICwtraGjA7jxBEEJCQjdu3ACDJklyYGAA4rBdXV2XL1+GGW/Xrl1f325CUD1uIyMjCHEMDAygHSdkH11dXSggA3VfvHjxjRs3jI2NCYKYNGnSvHnzZGVlN2/eTJ0qkdzs3buXenRheHg4ODgYxbjHTEVIuFlZWadPn87Ly4scChsbG+rgZzKZWVlZ/Pz8v/zyS2FhoZKSEtjNtWvXkKdWXFy8ePHiH374gU6nDw8P6+jogGfNwsLCxcWlra1dXFwMKWEHUkBAABxkKMDx48chNPEV4W5sbKROUdS6/EfhZmNj4+fn5+bm5uDgQCdexvAl4Ub7pUuXLkXR2+joaGFh4aCgoNTUVIhpsrCwXLhwAY2xlpYWPT09aKjPCjc6+PH8+XMhIaGLFy+Wl5cjSTUyMkLWVVFRsWbNGmlp6erq6pMnT4J5rFixYuPGjVu3bs3JyYmNjf1G4YZNv8OHD8vJycGg2Llz59u3b0dHR+GuyMhIBQWFgIAAFJUmCMLY2BhJJFW4hYSE9PT0Tp48qaOjIysrCwUbI9zJycn8/PyHDx+ura1FCyZtbW3oboiBNDU12dnZ/fDDD9QZXUZGJj09HUrV0dFx8OBBiHqbmJhAE3Fzc8PW6Hg+ffp09OhRFOOmCvfatWsbGhogLInkj4ODg5OTE+27jPe4h4eHAwMDkXA7Ojqi0NZ44Y6OjkbCffLkSRDuBQsWlJWVdXV1Xbx4ES06OTg4WFlZjY2NYTfI398ffmJlZZ08efLkyZM5OTkvXrxIPQhIkmR+fr66ujoqDNRRXV0dmvRLwv3+/XsJCYkrV66EhYXB9M/CwmJqakrdokf8buEuLS1VUlICC+Pg4JCSkqJ608PDw35+frAMERQUTEhI8Pb2/uGHHyCuMjw8DHLW3d1NjXFTu/DcuXNIC4aGhgwNDWGe0NHRgWZ1cHBgY2NjYWERERFxcnICu4GAg66ublJS0qlTp0AKJSQkbt26BVl9PdJNFe4LFy5AZKC4uHjt2rVQyM2bN0OIg8lkZmZmQrCClZWVnZ193bp1Hz9+9PPzg5QsLCwCAgK+vr7USRjJzcWLF6nd0N/fb2dnB36TiooKMl8ACffUqVPPnDljYGCATOG3334Dzx25hMbGxhwcHLq6urdu3dq6dSuY1+rVq1FYsKioaOHChfPnz4fZ7uPHj+h8DkEQs2fPvnv37ujo6MePH9va2rq7ux8/fmxsbIxWlJMmTYKO/opwj4yMwMkE4vcLt6io6M2bNy9fvszHxzfm6B7is8I9OjqKdkSXLVsGh6s6Ojr27t3LxsZmY2MTExOD1r/UBqmrq9uxYwdcR8KNwkoFBQVwZKKjowO0+PDhw7dv3965cyfUgnqI6OPHj3DYrqWlpbCwEPSUjY2NlZVVV1eXwWBERkYiEfm6cE+dOvXixYvd3d2ZmZnQ+JycnKDdJEl++vRJS0uLm5v7woULfn5+KNItLy+PjIcq3KtWrerp6enp6WlubtbV1YWSU4V7cHDQ0tKSIAhVVVV/f3907mjatGnQufAGQ0ZGBsS1TU1N58yZgw7JmJiYwBZxREQEFxeXvLx8XFzclStX0FhwcXFBAUMqbW1tZ8+e/ZJwg3NTUFCwZs0aZKJsbGxfEe6+vj5ra2s0r6SkpBgYGMDfAgICXl5e6NGwkwz7ZARBXLp0iSTJy5cvy8rKwjRTVVW1c+dOgsIvv/wCwn3nzh1YqvLy8h47dgyOP+nr64OrNzIyMjIyMjQ0RKfTm5ubPT09Fy1ahIrExsYGS2oU2aMKd2dnp4GBATc3d3R0dGVlJWybEQSxdu3aMXvFwB955f3YsWOoSjt37qTuY9DpdB8fHzA4Dg6O+Pj4Z8+ebd26Fd4UcHR0PHToEJ1Or6mpQYuyCxcu5OXlgamxsLDMmDHD1NQU5XbmzBkQ7u3bt8Oh0RcvXsyfP58gCHZ29tOnT8NJ++3bt7Oxsc2YMUNMTIyfnx88U1ZWVjU1NcjqG4WbhYVFU1MT3k95/vw52n02NDQcHR1FKrlv3z7k/F64cAGi/+jIjaysLNosBpDcXLt2jXq9vb396NGj4AetWbNmvHDD5uSUKVNu3LhRX1+PpJaPjy80NJT8l1dYUFAgISHBxsbGx8cnLCw8ffp0GFocHBy+vr6QW3Fx8VnS00IAACAASURBVKJFi5BwkyRJXdfDTkhpaammpiacRidJsqurKzg4GPWUs7Mz+VXhLi0thQNzxO8XbnFx8YcPHyYmJkpKSsJhrPF8dnPyw4cP1BOiYI1ZWVl8fHysrKwCAgLi4uKTJ09GGmFlZQW5UR3MrVu3ojMnJEk+efJkx44dsDGTnZ0NUjV9+nRhYWFeXl7wG8B/h6xaW1tPnDghISHR3t7OZDJReaZOnQpbZ98eKpk1axbsOff09KA4LxsbG3T37du3J0+eLCgoePjwYV1dXTU1NbBDNjY2f39/yJYq3OhUCZPJNDQ0hCUUVbgzMjLQMYm1a9fy8vIiJ/fYsWNNTU0dHR2ampp79uyBzHt7e1+8eLF3717oSjj5QKfTQUm5ubnFxcUFBQVRJqtWrYLNgDEDEHaGwfKpwq2pqblu3ToQbti2Qa4DOzt7YWEhJBsv3G1tbVpaWpDh9OnT8/LygoODQZ25ubmtra2ppnj69Gm0UxUQEECS5MWLFxcsWIDWB2/evIHuAM6ePQsLGicnJ3iEmJjY3bt33759KyIiYmBg0NXVVVdXFx4e/uDBg1OnTjk4OJAkOTQ0VFdXFxERgfZa4cwFcm6owp2ZmcnHx8fGxiYlJSUjI4NcNF5eXupyAfFHhDsyMhL8ZUlJSeTSIvuIiYmBUAlBEIGBgf39/ZWVlf39/cXFxXJycitWrKDRaI8fP0YxeENDw4GBgcTERNiuJQhCXl4e3B8Gg2FkZIQCc7AJEB0dDUEoDg6On3/+mU6nv3jxAvy1zMzM1NTUzMxMS0tLSCMiIhIZGfkfa1RZWQmDjYODw9bWFpxZe3t78NxlZGQePnxIUl7Gi42NBadbRkbm+fPnJEn29PTAgp2FheXAgQNj9mS2b98OVRsj3F1dXadPn4axp6ysPOZULPVUibW19ejoaEpKClodL1u2DB49MDBgbW0tLi4eFxeXmZmZnp6enZ198OBBsLDdu3dD8Prdu3cKCgrz589HHhCTyfTz8wN1gOPqYK9KSkroJbTh4eEzZ86A1wAa5OPjg4QbXlVA5OXlUbdAqD8NDg7q6+vDaFdUVETbjyEhIZBeREQkLi6ura3N19cXFHk8tbW1qCXV1NTgeKKHhweMz6lTp9rY2ECrnjt3bt68eYmJiRkZGWlpaenp6ejIgaqqKmj0p0+fkGOFjmoBFy9eFBUVffjwIY1Gu3LlirCwMLyiCW2LXmjYsGEDDPWBgQELCwtJSUkY3h4eHhDQU1FRgRVAeHg4Eu6YmJjxbkRCQgI65QlzbU9PD9orkpaWhr4+fvw4HHX9+PFjeXl5Xl7e9u3bYZJWU1ODUVNXV4dCfCoqKpA/nU5Hp3okJCTQboqLiws3N/dvv/2Wm5tbWFj46tWr06dPg2pISUmlpqb29PSoqqoKCAg8ePAAlfb169dQtjNnztBotKdPny5evNjQ0DAnJyctLS0jI8Pe3h6GLQcHx5jTTagr9+7di2ZTZPmamprr169HBjA6OhoYGAjazcbGhoQbvVGxatUquFhfX4/WVQcOHPj06dOnT59gu4sgiOPHj6NH9/T0oJ0YVVVVePTFixfl5ORQtJAkyQcPHqAtWQsLCwgV2NnZIeO/f/9+X1/fzZs3nz9/Pjo6amlpuW3bNi8vr02bNi1ZsgRNRXQ63cbGBsa4j4/PmzdvkHOzadMmcEZpNNq1a9f4+Phu376dlpb24sWL1NRUtNzX1tYeE4oh/5hw9/T0gO3u379//JE7T09PtAyxtbWF9yxiY2O3bNnCw8MDsYLAwEC0Oaajo9Pe3k6n0x0cHEAgODk5jx8/Do7huXPnwNpAJioqKpA3MW3atJCQkPr6+p07d86bN4862uEiQRCsrKxr165FLy9QoZ5sr6qqgrUJJycnvPYWFRUFEwkPD4+9vf2YtxVaW1vhUJ2enh56vd7f358gCFFR0fDwcPQI+O+mTZugzKdPn6aeTR4ZGbG3t4daL1y4EOwGlSorKwsicRwcHKdPn4YYi729PfJBdHR0BgcHKysrZWVlZWVlqbW7ceMGTF1TpkyB+b+0tFRSUnL27Nno9QSSJPv6+uAVmA0bNlRVVZWVla1Zs4adnf3o0aOgbiRJwgnI9evXwwTg7OwMT5eQkEDHsYGSkhI0JE6fPj2mEX7++WcQbklJSbQRj6YBYWFhmAYGBgbGH0VAJ5TRxADnuD98+ICOul+6dAmWShkZGUJCQvv376fmYGFhAU+fOXOmk5MTSZLt7e3wbhFBEHPmzAkPD3/z5k1RUZGzs7OQkJCiomJZWVlGRoagoOD69eupWbm5uYH1cnNzm5mZkSTZ0dGhoaEhIiIC6l9dXQ3vg8DrDiTlRB0/Pz81fIcsKjo6GrSem5v71KlTqamp5ubmyCu0s7MbGhq6e/cuPz//nj17qIUJCAiAjp48ebKjoyNJkjU1NSi8u3LlShSIP3ToEEg8HBUlSbK4uHj58uVSUlLUMySJiYkgyqysrIcPH87KyjI0NCQIQkZGBgVFExISeHl5eXh4Hj16RJLk8ePHeXl50ZuuJEnW1taiLb7169dTj6CgBGgq5eDggCmntrZWRUVFTk4OZjt0+Ade6iEIAoVK0DnuxYsXv3r1qq6u7ty5czANrF+//vXr12BCSUlJcORBWloa4loMBsPS0hJG3Jw5cxITE2FYnTt3TlhYmHo6YGRkxMrKCjYJbW1toR+dnJzgudOnT0fHtBsbG729vcXFxWVkZHx8fPbt28fOzn7w4EF0fszLy4uVlZWTk/P169c0Gm3Xrl2QyZYtW2CU5eXlycnJqaioUMNKZmZmYLFCQkLoWAviD34d0NHRUVFR0cfHh6QoYEdHh66uLor6EwQhICCwfPlyeXl5Pj4+4l/vp129ehW5jWCpGhoa+fn5bW1taCIlCGL16tWbN2+mHo6ZP38+HGGeOXOmlpZWbGzs27dv0bykp6dXXV3NZDIbGxuvXLmC1I0gCA0NDeoBDADKPDw8DK/DoMQiIiIrV67k4+Pj4+M7evRoREQEVemA4eFhiBiGhoYilUlOThYWFlZRUUGxI3gT58cff0THg6ZMmXLhwgXwZ9va2kxNTVGAhSCI5cuXQ5RgcHDQz88PKotu1NTUbGxsbG9vP3HiBLqurKyMAp0GBgbgF8TExFDvFREROXr0KPI+jhw5Qn2Fur6+fuPGjWvXrq2rq2tpadHV1eXi4po/f/6SJUt+/PFHdXX1WbNmqampZWdnFxQU6Ovro+UUQRCrVq1KSUkBfyo9PX3nzp1ojczHx+fm5gaPaG1tPXbsGJrOCYJQUFCIiooKCgpCq0iCIFasWDH+9V9EUVERmv8IguDi4lJWVpaTk+Ph4VmxYoWLiwsciYuJiYFIGj8/v5mZGTgW9+7dQ6fXwX50dXV1dHSoW23CwsI//PDDDz/8AJ2lpKRka2sL6+UpU6bo6upCHPPRo0foXVmCIERFRX/99Vd0gGHdunVNTU1MJnPXrl2LFy8uKioqLy/X19cHUQbmzJnj7u4OBglG6OnpSV2YT5o0CQJfM2bMWLNmzfXr11tbW58+fQou+bRp0yDaMzw8HB8fj3offjpy5MiOHTvQ3hpBEIcPH05NTd29ezeaBgiCkJWVvXDhApq3NDQ0ILj39u1b9NYl4Onp6eDgwM3NvXbtWgkJCVVVVVVVVQkJiZUrV4aFhX369AltIa5cuRK88tbWVvS6A6Crq0td0OTm5m7YsAEFGwmCWL58eXJyMnqnUU1NjTqXNDY2Qqmys7N7enrOnTsHegIsXLhQUVGRlZV10aJFly9fpr53xmAwHjx4AIFyYWFhdXX1TZs2Qf9u37794cOHQ0NDXV1d7u7uYNWbNm2i7q+0t7dDWMPR0bGrqyskJASmAWQw6urqGhoaa9euhaX5pk2bIiMjYYcJ3sXX19fX19eXlJQUFxd3cnIqKyuzsrJC0sTHx6enp3f16lUQMUFBwYiICFju5+XlUa1dXl4eTusi/ohwM5nM6urq1NTUhoYG2HRGbzR4eXnZ29t7eHjAd6Nu3LhhZWVlY2Njb2/v7u4eHR396dOnqKgo+F9PT09PT08nJycvLy8IhFVXV3t7e3t4eLi4uFhaWpqbmzs4OHh6enp4eLi7u9va2lpbW7u7u8fGxsIU3dvbe+PGDVdXV1dX1+Dg4ObmZiaT2d7eHhUV5ejoCPm7urq6ubmN3yGB+WZkZCQtLc3KysrV1RUeZG9vb2FhYW9vf+/ePeTFj1nbMhiMwsLC0NBQ5G4zmUz4Wg20L2Q+OjqalpZ2/fp1FxcXaBNHR8eIiAhYAfT09ISHh6PmcnNzs7OzKy0tZTKZdDo9OTnZ2toamhFudHV1hZV4WVlZYGCgh4eHs7OzpaUltImrq6ufn9/g4CBsn0KLwe1ubm4uLi7Ozs5ubm6urq4BAQHoxAvUKycnJz4+vru7e3h4ODc3NzIyMiEhwdLS8scff9y8ebO9vT0sJ2tqary9ve3t7aFh3d3dXVxcioqKIPpfWlrq5eUFzejp6eno6AgRcCaT2dXV5eXl5eDgAOVxd3e/fv16Wlra06dPr1+/Ts3t48eP45fVkEl1dTX0NWTi7OxsYWFhbW0dHBycmZkJfuXIyEhmZqatra2Hh4eTk1NUVFRfXx+TyczIyHBzc/P8F87Ozp6enr6+vs7OzqhI9vb2tra2NjY2UM779+8nJSXZ2tpCei8vr56eHiaTmZub6+XlBW3r4eEBn3Py8fFxcXFxd3e/ceMGrGrT0tJevnw5ODhYX1/v5+d348YNVM0bN24kJiYODAwgj/vRo0d2dnYoTycnJzs7OxcXl+jo6OzsbBjJ+fn5Xl5eMF4iIyPBdHNychwcHNBQgsHi7u4OFfT09HRxcbl582ZxcfGNGzecnJxQCzg5OQUHB8PXvtzc3Hx9fWG+qa6udnd3R23l4uJSWFj4/v37yMjIgoICNzc3fX39o0eP2tjYQLBrcHDw9u3bTk5O8DG17OxsJpPZ3d0dGRmJRMDNzS0iIgKdNGcymeXl5devX0eF9PDwsLKyKigoiIyMhNHq6+v77t07NOiYTGZOTo6/v39zc3N/f39QUBB1dNvY2FhZWbm7u6empqL9G9j6gj9ev37t4OBw5MiRzZs3q6urm5qaBgcHo3B2X1+fu7v7zp07dXR0LCwsysrKqCuhd+/eXb58OTMzc2BgICgoaP/+/YcOHTp8+PChQ4c0NDS2bdu2bds2NTW1vXv36uvrJyQk1NfXBwQEODk53b1798SJEwcPHjx27JiBgcH9+/fpdHpnZ+elS5f27NkDORw4cODChQv29vYHDhw4ePDgoUOHgoKCYGzC5qqWltahQ4e0tLR++ukniNYi/qBwjxlUfyCTr2f712TyjYm/Jdn4NvnD1fn6jf8x29/bAl9J39jYiI7c/bFM/kA7jE//jZl8Kdn3ss9vz+p3Jfu91vW7HvG7+MY8x3zM6/dm8u0l/2N1RGYwxh46OjpqamrGvMwJCbq7uysrKxsbG9ELqNR7h4aG4HpXV1dlZWVdXV19fX19fX3dv4PC0MPDwyjIU1lZWVNTQ/UaW1paampq4Pbq6ur29vaBgYGampra2tq6ujp4gR5KC+/swH/r6+upL8GR+B9SwGAwmAkHFm4MBoOZYGDhxmAwmAkGFm4MBoOZYGDhxmAwmAkGFm4MBoOZYGDhxmAwmAkGFm4MBoOZYGDhxmAwmAkGFm4MBoOZYGDhxmAwmAkGFm4MBoOZYGDhxmAwmAkGFm4MBoOZYGDhxmAwmAkGFm4MBoOZYGDhxmAwmAkGFm4MBoOZYGDhxmAwmAkGFm4MBvMZ0D94PTIy8if/GVXMdwcLNwaD+Qwg0yUlJYWFhSRJMhgMLNz/O2DhxmAwn4HJZDIYjK6urs7OTuxx/6+BhRvzv8Jn1eHrkjHm198rLn9Sj/7ZWgbCjf7+B9d0IoKFG/O/wmfV4euSQRUXdOUPPPf33oJuxIqG+VvAwo3536Kvry8lJSUgICAxMbGjowMuNjY23r1799mzZ59V9ra2tidPnjx9+hSl/0ZGRkba2tpGRka+/Zb6+vrKysqXL18WFBQMDw+Tf0L3MZg/DBZuzN8P0r7MzMyffvpp7969J06cUFdXP3bsGOyMpaenz58/X1VVFVKO0conT54sX758//791dXV5Dc4wvBTT0+Pra2tu7t7b2/v+DSdnZ0xMTF3794dc93d3X3v3r2bN2/29vYeHByE3Orr6z08PJ4/fw5SPr5eQF1dXUBAQG1t7Wd//eyVMRezs7M9PDzevn372QQ9PT23bt2Kjo6GgmH+wWDhxvzNgO6Mjo4mJSWtXr166dKl7u7uhYWFV69e5eDgOHXqFI1GS05O5ubm3rp162elLSwsjI2NTU1NDSnpf/SCR0ZGwsLCJk2atGPHjvb29vEJamtr9+/fv337dmohSZI8d+4cQRBLly5NTU0dHR2FiwUFBYqKimZmZgMDA2Py6erqevnyZUlJCUmSRUVF69evf/HixZg8SZIcE/D5Ev7+/osWLQoPD//sr11dXVu2bNHW1u7r6/uW3DATFyzcmL8Z0K/CwkJ5eXkxMbHMzEy4/uHDh5UrV0pJSeXm5t69e3fmzJn29vbwU2dnZ2FhYWNjI+idm5vbpEmTLCwsaDRaRUUFSZIMBqOzs7OzsxNp6xgyMzMXLVrExsamr6/f3d3d09PT2dkJhenp6RkcHCwtLXV0dAwJCaEWkiTJixcvcnBwWFtbQ86jo6M0Gq2wsNDW1jY7O3t4eLiqqio3N7ekpGRgYKCjo8Pe3l5GRsbCwqK3tzc9Pd3a2vrZs2cVFRUdHR2jo6NDQ0M1NTVo5qisrMzKyqqrqyNJsr+//+PHj/B3dXV1dXV1e3t7WFiYvb39+/fvq6qq3r9/T6PR2tvbS0pKaDTa4OBgWVmZo6Pj/fv3v3EawExcsHBj/n46Ozv19fW5uLisra2R01paWrpmzRp+fv7w8PDr168LCwsnJiYODg6+fv3ayspKXV399OnTVVVVJEnq6elNmTLFysrKzMxs3759xcXF7e3tV65cMTExaWlpQU9BnvjHjx8PHjw4bdq0adOmeXt702i0O3fumJiYxMbG3rx5087O7uHDh1ZWVr/99ltDQwO6lyTJoaEhVVVVERGRJ0+ewHU6nZ6RkXHmzBljY+OhoaFXr17p6empqKisXbu2oKAgKSlJWFiYIAg7O7u0tLSdO3eeOHHCxcVl//79Fy5caGlpKSoqOnLkSHx8PJ1OT0hIOH36tLq6+qlTpzIzM0tKSo4dO3bs2DE/Pz8NDQ1LS8vQ0NCtW7c6OzsPDAyYmZmpq6sHBgaamJhs2rTpzp07WVlZRkZGBgYG4N1j/tlg4cb8zYyOjj5//pyLi0tcXLysrAxdz8nJUVBQUFBQCAkJ0dbWXrZsWW1tbVJS0sKFCzU0NJYtW0YQxOPHj3t7e3fu3MnFxaWgoCAoKMjNzW1nZ1dXV6eqqrphw4aamhrIDZ0/GRgYsLa2XrJkyeHDhwUFBSMjIwcGBk6cOMHCwkIQBBcX17p1665du7ZixQoZGZn8/HxqUbOysubMmaOiokIVx5CQEIIgVq1a1dTUdOTIEUFBwW3btgkLCyclJd26dYsgiMWLF798+RKSrVixwsnJSVBQkCCIvLy8xMREPj4+JyenuLg4aWlpLS0ta2trMTGxHTt2ZGdni4qKEgTBzc0tKCh4/fp1CwsLgiCMjIygwKysrHJycosXL+bk5Ny6dWtUVNTy5culpKSeP3/+l/Qb5u8ECzfmb6a7u/vKlSsEQfz44489PT3ourOzMzs7u5GRUVRU1Ny5c/X19VtbWw8cOLBgwYLg4GAVFZWlS5e+f//+zp07M2bMmDx5sqmpqYmJiaCgYEREBJPJHBgYoNFo1JPIJEkyGIyAgIDVq1dbWFgcPXpUQEDg7t27dDrd0NCQIIg1a9YYGxs/ffr0yZMnCxYs2LhxI3XfcnR01N7enpub+/Tp0yi4MTIyEhoaShCEiYlJd3e3oaHh5MmTr1+/7ubm9vHjx6tXr7KxsdnZ2TEYDCsrK3Z2dlNT0+bm5sOHD3NychYUFMTHx2/ZsuXcuXPr16+Xk5PLzc2tqKhYvHjx3LlzU1JSREREJk2adP78+aioqM7OTnNz88mTJ/v4+HR2dh46dIggiI0bN4aFhUlISBgbG6enpy9evFhTUxOtEjD/YLBwY/5muru7L1++zMrKevz4cRQn6ejo2LhxIxsb26NHj7y9vdnY2Hx9fXNzczk5Obm5uWVkZAwNDbOyskZHR42NjQmCOH78+KtXr3bt2iUrK1taWkrNn3rWOz09fc2aNVJSUps2bZo6daqQkFBWVhaNRlNUVGRnZ09ISBgYGGAwGKGhoaKioufOnaPuHzKZzMOHD7Oxsd28eROu1NTUpKennz17lp+f/9atWyMjI8XFxUpKSmJiYi9fvuzq6tq6deusWbNevnzZ3t6uoaEhJSVVUFBAp9MvXbrEy8v79OnTvXv3Xr582cLCgoeHx8TEhCTJvLy8efPmKSkpubq6CgsLGxoaNjU1MRiM1tZWdXX1+fPnFxUV5efni4mJzZs378mTJ4GBgWJiYvHx8UFBQdOnT3dxcSHxCcX/B2DhxvzNgFASBKGqqtrV1UWSZGtrq46OzqRJk/T19UtKSg4dOsTLy+vv74+CEunp6aWlpfX19T09Pdu3b582bVpycvLLly95eHiUlJRaWlqGh4dHR0dBstFHNiC0vW/fvqqqqpSUFBkZGSkpqcbGxidPnsycOVNDQ+PTp08kSfb19Z06dYqFhcXY2Bh53Ewms6+vb+HChdLS0llZWSRJPnnyRE9P7/Lly9ra2iIiIo6OjkFBQQ8ePLCyspo2bZqVlVVoaKi0tPTs2bMzMzOzs7Nnzpw5e/bsoqKi0dHR8PDwmTNnioiIqKqqlpeX//rrr2xsbKGhoXQ6/cKFC7NmzTIzM9u1axcfH9/r16+hAAkJCZKSkpKSkllZWTExMZycnNevX6+vr1+yZAk7O/uzZ8+OHj0KwfS/pxcxfy1YuDF/P8XFxYqKijNnzvTx8UlOTj5w4MCUKVMMDAza2tqys7OXLl3Kysp6/vz5zMxMAQEBGRkZY2NjFRWV8PDwvLy8hQsX7t69e2hoKDAwEMId8fHxO3bscHJyotFo6BEfP348cOAALy8v+MsvX77k5+cXFBSMiYm5cuXKlClTYmJi4KBITU3Nrl27CII4dOhQd3c33F5fX3/lyhUuLq7p06d7enoGBQXJyclt2rTJxcVlxYoVM2bM2Llzp7CwsJKSkpGREVTE09NzxowZbGxsgYGBCQkJBEHA00dGRu7fvz9jxgxJSUnY5PTx8ZkyZYqGhoaNjc2cOXOMjIxycnKEhYVVVFQaGxuhAH5+ftOmTRMSEnJ3d//1119nzZpVUlJSV1fHxcVFEERkZOTq1asJgvjtt9/GH0nE/PPAwo35+6HT6YWFhfb29gcOHNDS0jpy5EhERERraytJkoWFhSdOnDh16lR+fn5fX5+Dg8P69ev379/v7u5eW1tbW1vr5OQE8vf8+XNNTU03N7e3b9/+9NNP7u7u/f396BFPnz7duHGjtrZ2eXn54OBgZGSkmpqapqZmQEBAZGSkp6dnc3MzpOzu7r5x48aRI0ceP34MUs5kMj9+/Oji4mJiYmJoaHj8+HE1NbXdu3cnJiaWlpaeP3/e0tIyOTlZTU1t2bJlO3bssLa2bm5ufvHihZaW1vnz56uqqiorKy0sLBwdHcGp9/X1FRMTc3d3hxhOQ0ODubn5hg0btLW13dzcGhsbOzs7LS0tk5KShoaGoFSvX7++evVqcHBweXn5gwcPwsPDR0ZGent7PTw8XF1dq6urfXx8LC0tc3JyYKnx13Yg5q8GCzfmfwUajfbq1auUlJTy8nK4wmAwent7KyoqYMONyWR2d3fn5eW9ffsWJG9kZKS7u5tOpzOZzN7e3srKyo6OjpGRkdra2qamJuqHpBsbG3NzcysrK0dHR4eHh+vr60tLS9+/f19XV9fV1TU0NAQRFZS4urqa+ip8f39/S0tLe3t7Y2NjTk4OFJLJZI6MjNTV1cEZ8A8fPmRnZ7969QoCPj09PeXl5W1tbVCR/v7+hoaGmJgYKysrFRUVJycnSAZ0dHS8fv06Ly8P3iGCelEPoQ8NDcHRb5IkBwcHoWwMBmNoaIhOp5Mk2dfXB1u7+PMp/x/Awo35HwXC09Qr4z8cSE38pRzGf0j6S2+Wj0/8Z74/Nf7vuLg4CHdYWlpSX24c8xRqGb7yWvyXPpCNP5z9/wEs3Jh/LN/4MZD/agGoOpudnW1qaurl5YW/JYL5k2DhxmAwmAkGFm4M5i8CHHAcysD8ebBwYzB/EfgfXsB8L7BwYzAYzAQDCzcGg8FMMLBwYzAYzAQDCzcGg8FMMLBwYzAYzAQDCzcGg8FMMLBwYzAYzAQDCzcGg8FMMLBwYzAYzAQDCzcGg8FMMLBwYzAYzAQDCzcGg8FMMLBwYzAYzAQDCzcGg8FMMLBwYzAYzAQDCzcGg8FMMLBwYzAYzAQDCzcGg8FMMLBwYzAYzAQDC/f3Z/w/Ktja2pqfn9/U1PRdMmcwGCRJ9vT0VFRUtLW1/fk8MRjMxAIL93+F7u5uc3PzlJSUkZERkiRtbW2XL18eGhr6XTJnMpnd3d02Njbr1q3z8PD4LnliMJgJBBbu7wN42fBfGo1mZ2c3bdo0Nze34eFhkiSPHz9OEASILPLHqbcAnZ2dNBptzE/UfxocJabRaFpaWgRB2NnZjSkDBoP5x4OF+/sAEQyQzsePH/Py8k6aNMnb2xs87qNHjyopKRUXF38lh1u3bpmZmdXV1Y3PeXzi0dHR48ePy8nJffjwAa6gp2MwmH88WLi/G6CbZWVle/fulZCQ4OXljYmJYTAYbW1tK1asvw01nwAAIABJREFUmDNnzuXLl729vfPy8kZGRgoKCtzd3R0dHUNCQnp6enx9fcXExLi5uc+dO3fz5s2UlJSMjAw/P7+CggKSJD99+hQWFmZnZ+fq6urj41NfX19cXLxgwYLdu3enpqY6OztHR0cjrxyDwfzjwcL9fQDR7O7utre337t3r6ampri4+Lt370iSTEhIkJCQmD59upiYGEEQR44cyc/PP3bsGD8//9y5c6dMmfL+/futW7eysLBs3bp13759HBwcc+bMmTNnDkEQV69eLS8v19fXX7JkibKysoiICEEQjx49un//voiIyL59+3R1dcXExK5evfp3NwAGg/nrwML93ejv77e3t1++fLmDg8OyZcsEBASam5tJkjQ3N58xY8b58+fj4uIWL16soqLi7e29cuVKNTW12NjYs2fPNjU16evri4mJ5ebm5ufny8jIcHJyKigoHDx4MDg4+MSJE/z8/MHBwSRJGhsbi4mJpaam+vn5ycrKQppnz5793VXHYDB/KVi4vxtRUVFSUlKKiop79+6dOnXq/Pnz29vbmUzm5s2blZSU3r9/39raunbt2nXr1j19+vTYsWMCAgK2trYkSXZ1dc2dO1dZWbm5udnR0ZGVlVVLSwuC3YmJiTNnztTV1SVJcnh4WFlZedOmTTk5OYcPHyYIgiCIY8eO/c3VxmAwfzlYuL8P7969O3LkyMGDB1NTU52cnDg4OA4dOjQwMNDQ0DBv3ryzZ8+OjIxER0fLy8sfOnSouLg4IyNjw4YNc+bMaWxsjIqKmjFjhoaGRkNDw8GDB6WlpVNTU0mS7OvrO3/+/MyZM+/du9fZ2env7y8gIGBsbJyYmAhBc0lJyW3btrW0tPT19f3dDYDBYP46sHD/KSC03dnZqaent2/fvra2tpGRkYSEBIIgVFRUGhoanj9/LiwsbGdnl5WVtW7dOk1NTXNz8x9//PHmzZuGhoZSUlJJSUknT55kYWERFha+efOmsrKytrZ2T08PZHvu3LkpU6b8/PPPly5dEhAQIAhCW1vb0tJSQUEhMDDQxcWFm5v75MmT8fHxf3dLYDCYvw4s3N8Bc3Pz6dOnq6mptba21tXVaWpqcnJyioiIREVFZWVlbdq0SVRUdO7cucePH6+urr579+7UqVOFhYWlpKQMDAwaGxvNzMz4+Ph++eWX9PT0X3755c6dO5Dt4OCgj4+PoKCgiIiIhobG8uXLpaSkrKysAgICTE1N379///Lly3nz5qmpqRUVFf29LYDBYP5KsHD/KeAQXmVlZV5eXkVFxdDQ0MDAwLt374qKioqKilpaWmg0WnV1dU5OTnZ2dmNjI0mSPT09BQUFr1+/zs/Pb2lpYTKZLS0txcXF7e3tdDq9ubm5t7eX/NfB8M7OzpKSkoKCgsrKyqqqqrKysra2tq6urvb29uHhYRqN9uHDh8rKyuHhYXwcEIP5/wMWbgwGg5lgYOHGYDCYCcY/RLipH/SgXvxK4vH3fq9Qw1dyY47juzzxP5bkfyeKMr48/ztl+xa+vT2pX5iZWHUEPjtM/sbykJ8bPn+mSP+l6owp2H+p3f45wv2Vj3V8th0HBwdramogyox++r5F+mwhP1sqkiSbm5tbW1upCf6rhfm7QI3AYDC6urqGhob+grI1NDQ0NTXBd2O+AoPBaGpqamxshE+D/UnG9O/g4GBVVVV7e/t/qYu/O1D+gYGB2tra1tZWkmJFvb29tbW1f/0h1O8+l7S2tn6LYXyJhoaG8Reppert7f0vfUTonyPc0Dr379+/fPnylStXrl+/7uzsfP369Z9//tnFxWVgYICaksFgxMTE7N+/38XFhSTJpqam73UwA/SopaXlS4UcHBxsbW3t7e2lemQZGRl6enre3t5wEPB70dXVVVFRAe8Bfcds/wxQ6/LycktLS2tr6+rq6v/2EwMDA7W1tf38/ODLi1/h+fPnx44ds7Gx+cqX01tbWysqKr6lm5hM5vDwcFlZWVlZ2eDg4KNHjzQ1Nf39/b/LrPCXkZycrKmpaWZm1tnZCVeYTOarV69++uknc3Nz2G//ywDjodFo7e3tNBrtTwp3Xl6evr6+i4tLR0fH7723oaHh2rVrurq6OTk542fioaGhlJQUMzMzS0vL/9LQ+4cIN1BZWamioqKgoLBkyRKCIKSkpE6dOiUpKamkpNTV1QVpkFZeuHCBIAgjIyMGg+Hh4bF169aampoxGY5p9C/9L9WARkZG7t+/f+rUqcrKys8WsqioyMzMLCoqipqPl5cXKyursbFxf3//f3wuldbW1vEPQukDAgI0NDQSEhI+W+Yv5fmVR4+/fYwHhP6m0WifPn36kkg9evRo5syZixcvLisr+2MF+HY0NTUJgrCwsKDT6dR8xmfl7+/Pysq6Y8eOz867gJWVlba2dk5OztfLCfT29p45c+bkyZMdHR2Ojo4EQRgYGCD/7vfW5bNruM+mbGho+Kwz+C33jsHFxYUgCHV19fb2drjCYDAiIiK4uLiUlZUrKiq+ntubN2+Q4n/l6Z+9/UumFRgYaGhomJWVRf6eyNX4rHx9fTk5OQ8ePAjria9XZAwFBQW8vLysrKxJSUmjo6NjijE0NGRmZkYQxObNm7+UM9Vv+wOL/n+UcIeFhRkZGdXU1MTFxXFzc1+5coUkyaSkpNu3b49JOTw8fPbsWQkJicTERJIkIyMjjx8/XlJSQv57233jqpb574Ga+Ph4TU3NwsLCzyZ++/btmTNn0GFtuD0iImLOnDmRkZFjEjMYDJDyz5anpaXF1NTUxMTkSwWLiIjQ0dFJS0tD9RpvGf+xjn/MZbh79+6FCxe+5Lo+e/Zs9uzZ2tra1KeMXwh/qSSjo6PfXhJTU1NxcfG4uLjP3kutflRUlIiIiIWFBTUBpEd3ubi46Ovrv3//fkyCzzI0NGRubm5iYtLT0+Ph4TF16lRPT0+SJEdGRtBdKOAwZsE+JltU9/7+/p6eHjgACle6u7up6dPT08+ePRsdHT2mMAwGA1UW3Ts4OEhNM36i9fDwmDlz5o0bN9AVOp0eEBAgJCQUGBg45q7BwUEoBpPJpNPpUVFR69evz83NRRWkGjNJkgMDA+PXLsPDw5/VeoS/v7+Ojk5GRgb5ZeP8FqP19fWdPn36H/uifVVVlZycnIKCAjT++Ke7u7uzs7NT2+378o8S7mfPnuXl5Q0NDZ05c0ZERCQ5OZnBYBQVFSUmJpaVldHp9JaWloyMjLa2tubm5rVr127YsKGoqCg3Nzc3N7etrW10dLS4uPjmzZu3bt16/vw5WE9jY2NISIiPj09aWlpJSUl/f39qampmZmZ7e3tOTk5aWlptbS2acvv7+3Nzc+/fv19YWEin07OysoKCgqqqqtLS0iIjI6urq1taWu7fv5+YmEg9eT06Onr06NE5c+aYmprGxcUVFRXB9fLycnd3dycnp6KiouHh4aqqqtu3bxcUFGRmZj569KiwsNDJyWnSpEnr16//9OlTbGzss2fPhoaGmpqacnJyuru7Kysrs7Ky6urq2tvbk5KSwsPDW1paRkZG6urqysrKYLCVlZUFBwdHR0dnZGTU1ta2t7enpaW9efMGyhkTE0NV3paWllevXhUVFQ0NDfX19eXn51dWVtbX12dnZ5eWlpaXl2dmZubl5bW2tmZlZa1Zs0ZUVPT27dsZGRmvX7/u6uoaHh4uKCgoLy8nSdLLy0tCQuLq1au5ubkvXrxobGyEmW90dPTjx4+ZmZnFxcUREREPHz6sr69/9+5dWloarIcYDEZOTo6Li0tYWFhtbW1nZ2d+fn5+fj5qZPgQLkmS79+/j42Njf4/9t46LMqu6xseGmGQGGCGTmlJCekOEVBAQMRARaSkEVAQEFERBBWRbpAOyaG7U7pRSro75vtjH/ccvOrl7XU9z/283+H7rL9gzn3uc+1ae+8Vv5WerqysrKio2N3dPTU19fHjx/fv39fX1+/u7i4uLhYXF799+7akpGRqaurg4MDU1JSDgyMyMrKmpqaysrK+vj4hISElJaWuri4mJmZwcLCpqamxsXFubm5mZiYzMzM1NTUtLS0gIKCsrGxjY2NpaenTp09xcXGlpaVfvnxZW1urq6v79OnT/Pz8/Pz8jRs32NjYsrKy4uLiPnz4ALSfxcXFT58+TU5OzsrKKikp6evry8rKam1tbWtr+/DhQ0pKClquHR8fb2xslJWVeXp6urq6ZmZmgh9bW1t9fX0jIyMjIiK6uroaGxuVlZWJiIh8fHxGRkbS09MLCwsPDg4mJiYiIyPRmg10bS9evAgNDe3u7l5bW/v06VNYWNiXL192d3c7OztHRka2t7ft7OwwMDAMDAxCQ0MrKipQKNTm5qapqSkvL29BQUFxcXF2dvbGxsbu7m5RUZGfn19oaGh+fn5/fz8SiaSlpYVAIEgkEuAYBwcHBwQENDU1HR4e7u3tNTY2+vv7P336FIlEVlVVTU5OHh0djY2NRUZGPn78OCcnZ2lpaWpqqq6urrW1FUz7iYmJ1tbWxsZGoNwA28Pg4GB1dXVHR8fh4WF/f39dXR3otMnJydLS0rKyspGRkbW1NbDSJyYmWlpampub9/f3r1+/DoFA7OzsqqurR0dHwYVsZWWlurq6qKiopqampqbmu53m8PCwvb0diUT6+/vj4uJaWVmh11FRUVFFRUVtbe309PT6+vrNmzfp6enLyspQKNTu7m5DQ0NhYWFVVVVdXd3U1FR/f39tbW1nZ2dTU1Nvb+/Ozk5PT09jY+Ovd6yT9IcI7pOHtYaGBg4ODgUFhZWVlfX1dTc3N1xcXENDw+Xl5WfPnkGh0Pz8/K6urjNnzlhbW7e1tQkJCZGQkISHh09PT0tJSVFSUsLhcEpKyrKysoWFBRMTEwQCwczMjIuLq6ysPDQ0BIfDsbCwHBwc+Pn5sbCwXF1d0crToaGhixcv4uHheXp6Tk1NUVNTQyAQBwcHOTk5TEzMyMjIzMxMTExMEA2PZn5tbY2DgwMTE5OFhYWEhOTChQujo6NDQ0P37t1jZWUlISEREBAA+FNERETS0tJnz549d+6co6OjlJQUAQGBhYWFp6cnBAIREhKam5tzd3dnYWFpaWnx8PDAxsZ2cHDIzc1lY2MjIiJ6//79wsKCsbGxoaHh7Ozs0NCQvLy8jIwMPz8/gJAtLS3FwcFhYGBwd3fn4eHBxcWNj48Hx7TDw8OEhARSUlIREZHR0VFwZPb09IyPj6ekpBQQELh8+TINDQ0nJ2dWVpazszMEAuHi4rp+/ToCgaCgoKisrOzr62NmZnZ0dDw8PLSysjp//ry1tTU/P7+MjExRURHoip2dHXNzc1xcXBEREVZWVjIyMmNjY01NTSwsLDs7u8PDw5ycHGlpaTY2NiwsrMePH9fW1kpISNDQ0Ghra/Py8mJjY1taWqJQqO7ubi0tLUlJSQ4ODggE8vTp06GhIQsLCw4ODlJSUmFh4a6urtDQ0FOnTrGysuLg4Pj5+X39+lVKSkpNTe3OnTvU1NQqKira2toQCISampqZmfn06dPv378XFhbGxsYOCgpKTEwEuLtwOJyOjo6RkREIcXJyclDho0ePamtrpaWliYmJCwsL29rauLm5ZWVl3d3daWlpFRQUxsbGMjIyzp49KysrC5i0t7f39PSEQqGqqqoKCgr4+PinTp0Ct0BAKSkpZ86cQSAQlJSUCgoKR0dH+fn58vLyGhoaADHY29vbzs4OAoHQ09N7eHiYmJhAIBBxcfHFxUULCwsYDIY+/KJQqE+fPnFxcVFTU9PQ0IiIiJSXl9PR0WFhYeXl5bW3twP4+I6ODmVlZVxcXAYGBnJycjY2tuHh4W/fvgkICMjJyenq6rKzs5uZmYFdQUhISFJSkoaGhpGRMTEx0d7eHh8fn42NLT09PSMjQ0FBQUxMjIKCQlFR8cuXL3FxcXx8fOfPn+fn58fExMTGxk5ISGhvb1dTUxMRETl37hwdHV1QUFBCQgIGBgY5OfmZM2fw8PACAwNlZWUxMDDCwsJAK1ZWVtzd3SEQCCcn58jIiKWlJS4ublNT09zc3N27d7m5uSkoKFRVVfPz83V1dcnIyNTU1KBQKBcXV09Pj5ycHAYGBgUFxenTp7W0tD5//ry8vOzm5kZPT8/CwoKJiUlAQNDb24vusZ2dneTkZElJSQYGBjw8PAoKisTExM3NzaKiIlVVVXZ29tOnT0MgkKCgoP7+fmZmZikpKRCRFxoaKiAgAGQIERHRx48fb9++DYFAwAzn5+cPDg4WFxcnJSXNzMz8zVP/HyK4T1JsbCwuLu7du3dRKNTy8rKjoyMWFtaNGze+fv2qpKQkKCjY398fFRXFysoaHh6+tbVlYGCAQCAaGhrGx8epqalv3Ljh5+f36NGj+vp6S0tLdnb2T58+1dbWsrCw6Ovrg0qAVLp9+zYMBnN2dkbfN+fm5sCPZWVls7OzlJSUEAhEQkLi/v37CAQiNDS0uroaCoVeunQJfWk9OjoqLy9HIBBSUlKDg4PXr18nIyPz9fU1MjJSVVX9+PEjAoHg5eWdn58PDg4mIiIiICAQERExNzd/8+aNqKiohobGt2/fnj9/Dpbo0NCQtLS0lJTU+Pj4mzdviIiIPnz4MDQ0JCIigoeH9+bNm9bWVkpKSktLy/b2dlVVVSkpqe7u7oCAAGxs7MDAwObmZnJycggEoqSkZGtrC4PBEhMTAatbW1tpaWn09PTnz5/v7Oz09vampKQsLCxsbm4mIyPDwMC4dOmSrKysiIhITU2Nt7c3Li7uy5cvi4uLVVRUGBgYurq63r59S0JCkpCQMD8/Ly8vz8XFdfnyZUdHx/n5+YODg+N/ufqAOa2oqKimpoaHhycuLn716lUYDGZmZtbU1MTOzn7r1q3k5GQGBoYHDx6MjIxcvHgRdLK+vj4FBcWdO3cGBwfV1dUNDAzGxsbMzc0xMTHz8vJcXFzExMRev3594cKFc+fOASYRCERCQoKWllZqampJSQkXFxcHB4eQkNDDhw83NjYSExMhEAgUCpWRkZGXl29ubjYzMyMjIwOt5uDgICMjS09Pz8zMxMLCun//fmBgIBwOj4iI0NfXDw0NbWxsFBYWZmZm7ujoSE5OxsbGZmdn5+fnT09PX19fT0tLo6Ojs7a23tnZuXPnDh4eXk5OTlJSEtgqbty4wcXFxcTEdNIGAKwylpaWAQEBbm5ura2t7Ozsd+/enZ6etrKywsDAyMvLS0xMxMDAsLOz29vbs7a2hkAgDx8+HB4e5uXlVVJSOmnF8fPzw8PDs7W1jYiI0NPTy8nJoaamJiEhGRwcfPv2LR4eXlpaWm5uLikpqYqKSnNzs7e3NyEhob+/f2NjIzU1NRMTk5iYWFpa2u7ublRUFAsLi5OT0/j4uImJCSsra1VV1aNHj0hJSePi4vLy8tjZ2U1NTWNjY7m5ue/du1deXk5JScnBwTE8PBwREUFAQCAjI1NRUXHt2jVqaurc3NzKykoYDGZgYFBfXw+BQLCwsKSlpc+fP19eXn737l0cHBy08vP4+LihoYGJiQkOh6elpYWGhjIwMFRVVZmamvLz8ycmJl67do2FhSUqKgpsaaSkpAwMDA4ODrGxsaAJMTExampqJCQkb968efLkCRQKff78eXt7OxER0dmzZ9HG8729vfDwcFZWVhcXl4qKCnZ2dk5OzsHBwbCwMAoKChUVldHRUV1dXQgEkpycnJqaiomJaWlpeXx8HBwcTEVF5evr297ezsbGxsnJ2d/f/+DBAwgEAoPBwNmOjo5OQEAACoVGRET8pu36TxPcx8fHFhYW+Pj4AMD66OgoOTmZgoLC19c3Pj6elpbWxcVlYWHhypUrrKyszc3No6Oj4uLiUlJSIFWNgoICCQnJixcvVldXgd4ZIK+mpqaysrKGhoZWVlaSkJCwsrIikciHDx/S09OfzD7T29srLS0tKCg4NzfX2dlJRkZGQUGRm5trZ2d37ty5+vr68PBwBAJxMsPv1taWq6srMTEx0LYbGRnR09MrKyszMTEpKytfvXpVTk4uJydnZWVFR0cHAwPD1tZ2fHx8c3MzMTGRjo7OwcEBhULl5uaSkJC4uLiEh4dTUVE9ffr06OjI0NCQkpKyvLx8enpaXl5eWFi4trbW1taWmpo6IyPj6dOnbGxs4KP37t3j4uIaGBjIyMjAxsYGcs3S0lJAQACcOEADQUaIW7dudXZ2Ahm9traWlJREQkIiKytbVVWloKBw4cKFsrIybW1tPj6+kZGR7u5uAQEBfX390dFRcLT8/PlzU1MTPz8/Dg6OmJhYeXk56AewPayurp4/fx4LCyspKUlfXx8LCyslJcXf35+GhsbPz+/BgweUlJROTk7Kysr6+voDAwMArYWKiqq4uDgwMJCKiurFixeWlpZnzpzp6ek5OjpSVlZmZ2f38fERFBRUVVU1NzeXlpZOTEzc29vLz88nJCQUFRXt6+vb3d19+vTp6dOnMTAwtLS0JiYm9vb2bG1tMTAwrl69Oj8/D25vQkJC/Pz84+Pjvr6+eHh4bm5ux8fHWVlZWFhYtra22dnZcDicjY2tpqZma2urrKwMmMe3traAqQoTE5ONjQ1ogeXl5RkZGVtbW/f29pSUlJSVlcvKyoyMjPDw8Dw8PJqbm6moqHR0dE6qqgoKCri4uOBweEhIyMzMjIWFBT09/efPn1EolJqa2rlz50ZHR+3t7bGxsaOiolAo1KtXr6ioqKKiot69eweDwVxdXU8qlMvLy/n5+eFwuJ+f3/Lycnd395kzZ65cudLS0iIiIgKy4nl7e1NQUERHR6NQqJCQEAQC8fHjx/DwcCIiIiwsLGCc3NvbU1RUVFFRWV9fHx8fV1VVvXTp0tjYmJycHAwG6+3tNTExwcXF1dDQkJCQuHTp0pcvX8rKyjAxMXl5eUdHR62trcnIyKKioqytrbGxsV1dXVEoVFlZGTk5uYKCQlRUFAYGhpqa2uTk5MrKSk9Pj4CAABsbG1BwA1pZWbGxsaGmpg4KCnr48OGDBw9evXrFyMhobGxsa2t7/vz5sLCw0tJSQUFBamrqpKSkhYWFjY2NBw8eYGFhffz48ejo6N69exQUFPr6+kxMTJcuXdrf329qaoLBYHfv3kU7nOTk5DAwMFy8eHFzc7OpqYmJiUldXb2qqgrct8A01tLSoqamLi4ufvToES0tbXV1dVtbGxMTk5qa2vLy8ufPn5mZmW1sbGpraxUUFIiIiMzMzLS0tCgoKJycnO7du0dDQ5OXl/f/1okbLTpHRkZERUUVFBSAOm9xcdHGxoaZmRmJRMrIyGBgYJSUlIyNjfHw8Ghqau7s7BQWFnJwcADzUVVVVXl5OTc3t5CQ0JcvX4yNjUlJScvKyubm5i5evCggINDY2Ojn50dAQODu7r62tiYrK6uiogKUtsf/ckZEIBC2trZra2v+/v7ExMRubm5TU1MKCgoKCgpNTU23b9/m4uICBnFAS0tLGhoasrKyX758QaFQCgoKt2/fNjc3x8DAUFFRycrKAkKkubkZgUDQ0tKi/RkcHR1hMFh6evrq6qq5uTkHB0dpaamamhouLm5NTQ0KhZKSklJSUgJqa3Z2dkNDw7y8PEJCQnDnEBISMjAwWFpaamlp4eDg0NXVHRwcNDMzg8FgMTEx9fX1TExM1tbWJ20vXl5eNDQ0AQEB/v7++Pj4Dg4OCwsLN2/eZGJiys3NRSKRdHR07u7uzc3N/Pz8V65cOTw8LC4uRiAQz549CwgIgMFgWlpas7OzYWFhQkJC3NzcIiIikZGRJ41m1dXVVFRUysrKGRkZIiIikpKSGRkZ6urqKioqFRUV4uLip0+fdnJySklJAd3l5+eHhYVlb2//7ds3AwMDJSWltLQ0RkbG27dvb29vFxQU0NDQXL9+/cGDB8TExCoqKvHx8fX19aurq1+/fm1sbHR3dyckJHRzc9vY2Lh27RohISEMBjt37lxFRUVXVxc7OzszM3NdXR3graioiJKS8t69e/v7+7dv32ZjY+vq6lpZWbl27RoVFVV6evrg4KC7uzsBAYGpqenKykpMTAw2Nra3t/fXr1/l5OQICQmpqKg4OTnX1tby8vJgMNj169dXV1eDg4PRwpqTk1NVVXVkZCQsLAwOh+fn56NNjs3NzW1tbYGBgZiYmIaGhjU1NUxMTEZGRuvr60gkkpqa2srKam5uTltbm52dvaOjY2xsTEFBQVhYuKioiI2NjYCAoLi4GN3PIyMjwLwBh8OlpKS+fv2amppKR0f36tWrBw8enDp1ytzcvK+vT0tLi5eX9/Pnz4uLi4aGhkJCQnV1derq6ggEgp2dnYmJqbGxMTMzExcXFxwggoKCCAgIHB0da2trKSkp5eXlOzo6REVFgftWbm4uSJHa19enqKiIj48PND93796dnZ2Vl5eHQCBAd+/i4oKFhaWtra2rq0tDQ1NYWAjYLisro6GhAd2Lnpbr6+seHh6EhIQiIiJiYmKlpaV6enoYGBji4uKBgYFtbW1bW1vBwcGYmJgGBgZAkX1wcCAnJ0dLS9vZ2Tk/Py8hIaGqqnr79u3Tp09HRERsbm5aWFiA2yG6/+/cuQOBQEJCQo6OjmxsbGhpaZ8+fWpubg6FQl+8eLG7u1taWsrAwACgOgUEBKSlpbu7u728vMjIyBITE3d2dpycnPDw8BISEqKiogDkZ2pqKtAdIZFITk5OGRmZf+sLhKY/TXDHx8fj4+NbW1uD31taWqipqQkJCTU0NHBxcSEQiJeX1/PnzykoKNjZ2auqqkJDQ3FwcBQUFIKDg2VkZLq6uoyNjXFwcOrq6gwMDPDx8Z8/f/7gwQMcHBxeXt6QkBAVFRVqampgp6KlpSUmJs7NzQXf2tnZ8fLygkAg58+fz8jIMDAwEBER6e3tTUtLQyAQhISEL1++vH79Oh4enpWVFZrz2dlZZmZmMzOzjY2Nt2/f8vKNQVkmAAAgAElEQVTyIpHIV69eQSAQY2PjqKgoFxeXwsJCLy8vQkJCGxsbcGgaGxtTV1fHwMAwMzMrLy8XFxcnISHR0tLCx8cHqd+rq6t5eHhsbGxQKNS7d+8wMTF5eHj4+PggEIigoGBBQQE9Pb2CgkJMTAyoR0NDIzY2VlRUVEJCYmNjIzw8HNzg0L6Gi4uL2traWFhYCgoKAgICEAhER0cnLy+Pl5fXyMhofn7ez88PBwdHR0fH0dGRhITk/PnzpaWlPj4++Pj4SkpKnJycEAhEWFh4bGzM2NiYj4/PwcFBRETkzJkzgYGB4Ct7e3sBAQEkJCTx8fEBAQE4ODj+/v4lJSV0dHQ0NDTXrl1jZmamoKAICQmJiYnx9vaemZnR1tYG51aw07CxsRkZGVFSUuro6Lx//56dnR1okISEhCAQyNWrV/Py8oB3v6enp5ubW0dHBzk5uaGhYX9/v5iYmL6+vo2NDRsbm4aGhqamJsgzB5bu3t4e0BXQ0dHl5uZevnxZQUFhenr648ePDAwM+vr6Pj4+Tk5O3d3dLCwsioqK8/Pz9+/fh0AgZmZmL1++pKSk1NbWtrGxISYm1tXVFRAQwMDAuHHjRnBwMODtxo0bFhYWZGRkoaGhc3Nzly5dwsHBsbCwAE54e3t7165d09PTKygoUFJSUlFRycvLIyUlFRcXDwoK4uHhgUAg165dA0/x8fFDQkKqqqrw8PCIiYmB3MTGxvb390d7sNjY2Ojo6CCRSG1tbW5u7tbWVn9/fxISEl1dXaDfExYWjoyMlJCQuHHjxvz8vLOzMwsLS2ZmZk9PDxUV1eXLl01NTQGIPKj/3r17ISEhQNUOUIvx8PBISEi8vb1ZWVlJSUlfvnwZHh7u5ORUV1c3OTmprq5OQkLi5eUF/AJQKJSamhoREVFVVVVjYyM7O7u+vn5kZCQlJaWGhgawEB4eHhoaGmJiYlJTU6NFOfgdKLUICAjCwsK2t7eBjsjIyAgoT9LT0y0tLU+fPo3WjDc3N9PR0enp6Y2Njbm5uTEzM3t7e9+5c4eCgiIgIMDX15eQkBAbG9vPzw9tvgJOpe7u7q6urlAolJSUVFVVlZqaGug3Pn36JCYmBoFAdHV1ra2tSUhI6OjoXr9+7eLiQkZG5uHh8eLFCzgcDoFAoqKiHj9+DG5FcXFxQCIVFRVBIBAeHp66urr/t07cgPLy8oAzg5GREbCAj4yMXLhwgZqa2s7OTktLi4yMLCQk5PXr1xQUFEZGRtPT076+vkRERBYWFtHR0YKCghwcHKysrCYmJnNzc0FBQadOnRIWFr537x4bG5ukpGRKSoqFhYWTk9POzk5tbS3wRG5rawNfPzw89PHxgUKhNjY2TU1Nenp6z58/39raqq2t5eLikpeXz8vLMzY2ZmVlTUxMRPO8trZmaGhIQ0MjLCyso6OTkZGxs7PT1tYmJSVFSkoqJSXl6ek5ODgYFBSkp6fX3t4OxvXLly/y8vI4ODjBwcFdXV1ycnI0NDQ3b94UEhIiJyePj48PDAzk4OAAV+bMzExBQcG7d+96enqeOnVKQkKisrJSW1sbXGAtLS2ZmZnv37+PRCJv374N1DghISFYWFh37txBXxXX1tbMzc1PnTplZmb26NEjXFzce/futba2amtrFxUVHR0dOTk5weFwHx+fDx8+0NDQaGpqDg4OAqupurq6u7v7qVOnpKSkpqamTExM7O3t+/v7r127RkRE9OLFCwCIuLGx4ePjo6urOzQ0FBsbe/fu3cHBwZqaGkZGRklJycrKyoCAACgUysTEZGBgkJyc3NPTY2Bg4OjouLOzU1xczMPDo62tnZ+ff+fOHXx8fFlZ2bt37xIQEBgZGWVnZ6uoqJw+fVpBQSEoKCg5OVlNTY2AgICPj4+fn//Tp0/t7e3a2trx8fG1tbWSkpLCwsL6+vry8vJop7rt7W1HR0dSUlIDA4OgoCABAQFCQkIhISE1NbXXr183NTUZGhpiYWGBKRQXF7e/v29gYAD8/96+fauoqFhYWNjS0sLPz8/Pz//u3bsLFy6wsLDo6OioqanR0dE9fvz45cuXmpqa/f39MzMzmpqaQIgAwbGxsWFlZUVDQyMoKCgmJubv7z89PW1nZyclJaWtra2vry8lJeXq6lpWVqampiYoKFhfX//582c1NTVFRUVra2tFRUVOTs6IiAh0GJqbmxsbG5uQkNCZM2c8PT3X19fDw8PhcLi+vr63tzfQmTQ1NT148ICamlpCQkJTUzM4OPjg4GB0dPTChQsFBQUtLS3a2toKCgo+Pj4iIiJUVFQuLi7q6upUVFQeHh5RUVFwOFxOTq6hoSE8PJyOjo6KikpJSendu3eLi4u1tbXAHsvPz6+trR0ZGQmclOTk5Dg4OM6ePXvlyhXgdyEtLQ3mMAqFOjg4uHbtGg4OjoqKSmdn58mFX1FRAYfDXV1dwc6UmZlJQUEBlqeXl1d9ff3NmzfPnTs3MjICyn/+/JmdnZ2UlJSPj09MTCwiImJmZgbMVUZGxnPnzmFgYJCQkPj7+6MFd3BwMAwGO336tKSkJBcXFwQC0dPTe/z4MRYWFg0NjaSkJCsrKwQC0dfXd3Z2hsPhAgIC6enpwAuejIxMSUmJiYkJCoWmpaVpaWmJiIg0NTXdv3+fkZGxpaUFnJP4+Piampp+U9b9UYJ7YGAgJyenvLy8vr4eHOL29/f7+vrKyspmZmYGBweRSOT8/Pz09HRhYSEYxcHBwaKioomJiYWFhYaGhoiIiLS0tKmpKRQK9e3bt9zc3Pz8/IGBgfr6+vr6+qWlpdHRUeC7trq6mp+f39raetKYMDo6WlhYOD09vb+/39bWNjMzc3x8vLOzA1wJt7e329vba2trd3d30a8cHR0NDQ0lJSWFhITU19eDHw8PDzs7O4FhBySunJ2dHRwcRF/c9vb26urqcnNzV1ZWgN8hcHv6/Plzc3Pz0tISsM6DTWV5ebmlpWV8fHxjYyM/P7+2tnZtba27uzs5ObmiouLr1681NTX9/f0bGxuDg4PgiPfly5dPnz6djIs7OjoaGBjIz88HfZWbmws8LLu7u4Fttru7u6SkZG5ubnl5ubS0FCyt4eHh9PT0jo6OlZWV/Pz8xsbGvb29np4eoOjo6ekpKioCSdpQKNTBwcHw8HB/fz+At52engaGh5KSEuDkt7GxkZ2dHRUVVV1dvbu7u7a21tnZCV5fWFiorq4G2ZlHR0eTkpJKSkpmZmaAJygKhert7Y2Pj8/KygJYu9XV1XFxcWFhYTU1Nbu7u6urq52dnQsLC9vb2w0NDbW1tf39/cBJDj0iPT09hYWFk5OTTk5O9PT0NjY24eHhSCQSrO3Gxsb4+PiwsLCSkhJwQmxtbS0sLAS+g52dnTs7O/v7+w0NDXV1dQcHB/39/dnZ2bW1tV1dXRUVFSCsvLe3d39/f3d3t6WlpaSkBL1rAolZWFiYkJBQVFQE4oNmZ2cbGxtra2vHxsa6urrGx8dXV1cbGxtbWlqOjo4AvHBPT8/8/HxPT09tbe1JdIevX79WVFQkJiZmZmaC2qamppBIZFdX1+bmJmg+cM1MSkqKjIxsamoCk3Zra6u7uxv83dfX19LSsr6+3trampqaOjAwMDg4CMzyMzMzxcXFwCVmb28PiUTGxMSUlJSsra3V19dLSkpeuXIlMzMTJHhCIBDAlNLa2hoREREfHw80KsvLyx0dHehOOD4+7unpycvLGxgY+M7JfWlpqbS0FF1yZWWluLg4Li4uMTFxbGzs4OAA3MnQmqLt7e3Kykr0eIElPDY2lpKSkpSUVFhYmJeXB8QC+pX5+XkkEhkbG1tVVdXU1JSent7T07OyspKVlRUdHZ2Tk1NZWZmRkdHR0TE6OopEIhsaGtbW1sbHx5OTkxMSEqqqqqqrqwsKCubm5qqqqpqbm7e2turr6ysrK/f29oaHh1NTU6urq38fReCPEtz/S52dnS4uLtbW1mfPnn3z5s13Xqj/S/91mpubExUV5eXlBZvE/9Lfpffv30MgEA0NjYGBgcTERGZmZjo6uv/tzL9Lf5rgPj5B/7YY+u//dh6++8RvcvJfpMPDw4aGBnV1dQ0NjfDw8JMGnN9h47+dn39M30UD/wOW/vGL/5YyMjL4+PjU1dVP3ta/C/j8/U//23n4/4fh+O+l7u5uFxcXPT29W7duubi42NnZpaWlbWxs/K1mfjc9flEG9R9Y4L9P/7lP/2mC+3foO7yu/+i4/s9DwX358uUfnF+Oj4+BdwdYCSc9Pf7n6bsR+VvC6z8t6drb25OSkjIzM9EaHvR3/0Gn/djSXxf4Y6i+vj4yMrKqquqkJuT3X/9ulH8c9D+139D0pwnu7e3txcXF1dXVv/JjP/4XrsjGxsbs7CxA6ftvZODg4GBlZWV+fh4oi38hRw4PD1dXV5eWlr7Di/i/Qj/y+X9XcG9ubi4sLKyvr6PhBH7/3aOjo93d3aWlpeXl5X+M2Pk7dHBwsLa2trS0dBK+6vDwcGVlZXl5+XciKY6Pj/f391dWVsA0+KkAWltb6+npAa4X/0toOjo6AjCB29vbfyW4Nzc3f3Mg/nO0tLR00qb130V/muBubW19/PhxeHj4X0X9o8e4qKjo/v37aWlpf1XVPxPoCwsLkZGRNjY2rq6u4+PjvxA6q6urMTExjx49qq6u/rvy5RfV7u3tra2tbW9v/13Ju7293dXVlZ+fX1hYODU19TvNB0awf/Ctf0vV1dWurq7R0dFgHP/WWOzs7BQVFbm6un78+PE/pOUH/LS3tz969Mjf3390dHR2dvbr16/AaOzu7h4YGAhM3P+W86WlpdDQUGdn58bGxp+WDwoKUlNTQyKR/4mGAPofO5/+1z+0uro6PT29u7s7NTUVFBTk5ORUUlLy05INDQ2enp4RERE/xYH6HQIHiH/M8/r6em5uroeHR2tr608r2dnZ+ceHtj9NcOfm5pKRkWlrawN/gF/coby8vDAwMACCILrkr++qP5b5sfz4+PilS5cgEIiMjAzaS+Snw7a8vHz79u1Tp07FxcWdPLL9+NG/evQjHR8fDw8Pv3r1qri4+O/u88vLy8ABloeHp6am5qc8fNcDa2triYmJ8fHxf0uf/iPP3/2BQqHCwsLw8PCMjIyAz8PfWjwbGxuurq6nTp16+fLljxjc3zXh+AR9VxJAq4PUByfLo3cp4IcrKira0dHh4+Njamo6Nzf39u1bAgICTU1NEC2N1j79FQOLi4vKysrExMSpqak/bc65c+cgEAga3fBHYP6fduBv0k9748eavyv/06c/rQT8sbKysrCwsLe392+znfwVJ2jKy8szMTFpbGwEUZSnTp06GYd8khwdHSEQiKGh4T/DuD84OKipqXFzc2tra/spJ0dHR+vr68vLy2A+/NhvXV1d3NzcZGRkAO0OPNrd3QX4YjMzM2/evAkNDQWy+++O3Z8muJFIJAsLy0mkU3SPnBRkANb1zJkz+fn56DLflTw6OgJeR+BSBg7F6DJ/tVWOjY2pqqrS0NCAiDv0Ufrw8PDksfTo6Gh6evr+/fu0tLRjY2PoOr/zFPyuCeh/wbX6ZHPQf/f09Ojp6UVFRaFbgfbe/TXt7+8/efKEkJAwODgYzcCvj9Kbm5tubm52dnYgMvvvTr5fVP7u3TtSUtIPHz78+Ojfbkirq6seHh4IBALtFYt+5bsvoscd/HFwcHByEY6Ojvr4+ISFhZ28D52sITc3l5iY+OrVq+vr69bW1gYGBgsLC+np6TAY7PXr1999CyhwTn4XhULt7++Pjo5KSEgAeBnwCBQDXG1ubgoICHBxcbW0tBwcHOzu7qKr3dzc3NnZQTP8a4UA+ulfocXu7+9/h1f+3R+on43vjzfF744gKBRqZWXFw8MjICAAaHu+q2R/fx+NBIv+5ce2oJ8mJCTIysrm5OTMzc1JS0uDwE7wCL1gAYEoNi8vL9Q/ouPj45CQEBERkYSEhJ8WWF5e/vDhQ1pa2l8l6Pj8+TMnJycPDw96yA4PDz9+/JicnLy3t9ff36+lpQXg3v4Be3+U4D46OnJ3d+fg4HB0dKyqqhodHUUP5JcvXxISEqqrqycnJ9fX1/v6+iQkJGRlZevq6mpqaurq6tBQSs3NzXFxcRUVFZWVlQAT9dOnT69fv87PzweTEoA0xsTEAM3jd5Ost7dXVFRUVlZ2bW1tYGAgPj4ewKVmZ2ej5cjY2FhmZqaPjw8/P7+Kisry8vLx8XF/f39ycnJ8fPzw8DDInFJUVDQ+Pv7169eCggK09/fm5mZ9fX1YWFh9ff3h4eH+/n5ra2tsbGxjY+PQ0BDwR66pqQE2n62trfLy8oiIiMbGxvn5+V+LvKGhISUlJS4uLoCOPzk5WVRUBBzJ9/b2RkZGmpubZ2dnV1ZWpqam1tbWDg4OpqamRkdHl5aW9vf3R0ZGcnNzOzo60Jrl4+Pj9fX1ycnJubm5w8PD7e3tb9++Ad3F+vp6Q0MDaOD29vbY2FhlZSXIHATy9VhYWHBxcb19+/bz58/A6RuFQu3v7/f396ekpIyMjExPT/8oI2ZmZpqamhISEuTk5M6dOwc8lwcGBuLi4gB47+fPn9fX12dnZ8fGxioqKpBIJPoevby8nJmZmZeXV1lZ2d/fv7y8/OTJEzgcbmFh8d0Qb29v19TUtLS02NjY4OPjv3r1amhoKD4+HhwqzczMsLCwXr16VVtbOzAwAObV/Px8cXHxx48fu7u7QW37+/vd3d3p6eleXl4IBMLMzAzwkJ+fn5WVNTw8XFFRsbm5WVpaSktLa2VlVVZWFhERAQAPgNtyREREREREcXHx8vJybW0tUHABB3Dg+49eFFNTUykpKaOjoxUVFVlZWdPT05OTk8XFxWjI+K9fv2ZkZADg38PDw4GBgcLCwtHR0a9fv5aUlHR2dgI9e2VlJTivLC0tLSwsAC/m1tbWsbGxpqam8fHxxsbGrKwsABkGPPq3t7cfP36Mg4NjaGg4OTmJ+tfO1N/fX1lZ2dPTEx4enpmZiU6NNjw8nJaWlp2dDWbdwMAAWLOlpaULCwsLCwtJSUl1dXV7e3vZ2dmkpKRXr15FD/2nT59yc3MnJiaAXltPT4+cnDwxMXFycnJqampxcRFkBwR3JnQWqpPDOj09/eXLl7m5OWBiGRsbGxkZWVxcBBnOtre319fXp6engQktOTkZoGWA8LH19fXOzs66urqhoSGwIgAWlaGh4dTU1MTExPT0dGZmJhMTk56eHgAZBtmp9vf3Z2Zmvn79Oj09vbi4+JtY83+U4J6cnFRRUcHDw0MgENTU1ADE/fj4uKGhQUZGBixmSkrKDx8+lJWVcXNzX7x40d3dHYFAyMvLr66ubm9vBwYGcnJySkpKMjExSUtLA3woBAIBg8FERUXb29t3d3cjIiJAGRYWFmVlZbRbGFiipaWlNDQ0NjY2s7OzqqqqxMTEDg4OhoaGMBjM2Nh4YWGhvb396tWr/Pz8jIyMUCj04cOHa2trpaWlqqqqly9f5uLiunPnTnNzs62tLQjdNjAwICMjY2Jimp6eXltb8/T01NbWpqWlBfwUFBTQ0tLC4XAODo5nz54lJyefPXv20qVLk5OTBwcHnp6esrKysrKy1NTU0tLSv47LKi8vBzghx8fH9fX18vLy8vLy1NTUvr6+Q0NDenp6tLS0zs7Opqam1NTU9vb2o6OjAgICHBwclZWVXV1dly9fpqWlpaKiunfvHliiBwcHMTExNDQ0/Pz8vb29xcXFfHx8wcHBKysrDx8+lJCQ4OLiunjxYm5u7u3bt1lZWU1NTcXExIyNjWdnZzU1NU+dOkVLSwuC3RcWFg4ODqKiomRkZAAnVFRUILwIfftubGzU19eXlJQUExMjISFxdHTc2NgoLS1VUVGRlpYGCJ+PHz/28PCAw+HU1NR0dHS0tLTu7u4gmZy+vr64uDgvLy8MBnNycoqPjychIcHAwLh79y4QtWB8Dw4OPDw8+Pj4REREiIiIBAUF3759q66uzsnJWV1dvbq6Ki0tDYFAqKioqKio9PX1x8bGxsfHzc3NxcXFeXh4BAQEvnz5cnR0FB0dffbs2YsXL3JxcUGh0Pj4+K2tLSsrKy4uritXrsDhcC4urpmZmeTkZDgc7ujoqKurS0VFlZqaurm5aWtry8XFpa2tDSLaCwoKxMXFZWRkzMzMBAUFycnJX79+jfrXKXVpaenhw4cIBEJSUpKRkZGMjMzKykpHRwcGg926dQsYNq5fv66srMzBwWFmZvbt27eLFy+SkpIaGRldvHgRBoPdvHkzKCiIhoaGh4enurp6bm5OVVVVX1//6dOnvLy8vLy83NzcPDw8ampqtLS0IJYY4BHa29tnZ2efPXsWAoHcunULjXRYWVnJzMxMRkZGR0eHQCDgcLi7u/vy8nJlZaW8vDwPDw8nJ+fLly87OjoYGRkZGRkvXbrEzs4eGhoK2HZ3d0ehUH5+fjAYDCSmGBoaunr1qpCQ0NmzZ+no6ExNTWtra2VlZdXU1G7evElLSysjI3Pjxg1GRkZxcfGNjQ0QwhoWFoaWkisrK8+ePWNlZWViYhIVFU1JSTE3N2dlZb1x40ZOTs7FixcRCIS7uzvAaLO2tu7q6oLBYJiYmBISEouLiysrK1ZWViwsLGAxXrt2rbe39+XLl0xMTM7OzgICAqysrBoaGvT09CBC8urVq7y8vDIyMgDhnZOTk5GRkZqa+t69e+hMQ7+mP0pwl5aWsrCwyMjItLS0AEjogIAAIIOcnJw6OjqMjY0hEEhaWlpMTAzAuHF2dpaRkQFQdgAoNSEhoaWl5cyZMwoKCrm5uTIyMlpaWm5ubkpKSuPj4yEhIezs7B8+fOjr62NlZRUQEOju7kb9a5Gsrq66uLiQkpJGRkYuLy8DfAMEAmFqasrIyKinpxcbGysjI3PlypXq6mpzc3MEAvHp06fCwkI+Pj4TE5OBgQEPD4/z58+np6e/ePECAoGwsbE9ePAAHx8fCoUODw8/fvxYVlb248ePSkpK9PT0SUlJAODC1tb20aNH5eXltbW1FBQUlpaWOzs77u7u7Ozs0dHRdXV1Z8+e5ebm/jWEzdu3bzEwMHx9ffv7+xUUFFxcXDIzM+FwuIODw87Ojr6+PgQC4eXlBaCDKioqk5OTwsLCUCi0p6cnLCwMCoV6enpeunTJwsICnIWPj48HBwe1tLSgUGh6enpnZyctLe2LFy9sbW3V1dVzcnKMjIw4OTmRSCQALCUkJJSTk3v8+DGAitbU1Ozo6Lh169apU6eSk5Ozs7NZWFhevXrV0NAAhUIpKCjAHRn0fFNTk7Kysq6ubnV1tYWFBRwOByHmQkJC9+7dGxoaUlVVBXv2rVu3ALJHcXExgF0dGRm5c+cOPz8/SAUAoFBLS0uhUCgAJDmpb/Xw8CAnJ3/z5k1UVBQuLu7169enp6e1tLQYGBhmZmZaWlpoaWlBVfr6+szMzKmpqa6urjIyMsHBwRwcHLS0tD09PXFxcczMzC4uLp8/f5aWlhYSEqqpqXF3d+fk5MzNzc3JyQHZwmZnZy0tLTk4OACGcGVl5fj4uKWlJQA9LywsxMLC0tDQGB4ePnv2LAYGhoSEBECbe/ToEXpYV1ZWnJycADChnJwcAQEBGRmZrKwsFAq1tLQECPLGxsYFBQUMDAza2trT09PCwsIAruTKlSsEBASGhobV1dV8fHxwODw7OzsxMZGMjOzhw4cfP35kY2MDRhFjY2NXV1ceHh5GRsaCgoIPHz4QExOHh4fn5OTQ09MrKiq2tLSgE0M3NjYyMDAQEBAEBgbW1tbKyMioqKgEBwefP3/ezs4uICAAHx/fzMysq6sLgAzz8/NfvHgxIyMDjB2AHNHT02NmZm5oaBgbG7t06ZKIiEhBQcGrV68ICQnt7OyCg4MZGBguX7587dq1mzdvlpWVOTg4AKTy2dlZe3t7CARyEoqvrKyMnp5eUlLS19dXQEAAiUT6+fnh4+M7OjouLS2pqKhAIBBKSkpZWVkYDKajo9Pb28vIyCgrK9vT03NwcHD9+nWAQg70MxcuXOjp6bG2tqampr516xYXF1d6ejqQGIyMjCCEmIeHR0JCoqOjw8XFhZKS0sbGRlhY2N/f/zfN6X+U4AbwlS9fvkShUOHh4YSEhM7OzhYWFry8vMDEf+/ePXl5+YmJCTCKFhYWSUlJgoKCxsbG5eXlZ86csbKy2tnZGRgYYGFhARgOhoaGVFRUQUFBo6OjXV1dgoKC169f39zc/PbtGwcHh62t7cko1aGhIUVFRWZm5omJiZWVFQDI4OvrGx0dzcPD4+7ubm1tDWb/5ubmzZs32dnZBwcHASwZMI4/efKEjY3txYsX9+7dw8TEtLa2zs7OJiYmVlVVLSsr4+XlVVZWNjIyEhERCQoKWlhYiI2NJSIi0tDQAKqDrKwsamrqsrKyrq4uenp6a2vrvb29qqoqNjY2ExOTkyrd74w/3759MzQ0pKOj+/Dhg7m5OQUFhZeXl66u7uXLl9vb2zc2NtTU1CAQyOvXr6Ojo6mpqT08PIaGhsCZcW1tbXBwkImJiYuLKykp6TtviqSkJCoqqujo6OLiYnl5+cePH4M7gaurq4CAwMuXL/v7+1VVVYmIiDw8PEZGRubn5wEkEMjuBhAyAwICjI2NVVRUNjc319fX6ejobt26hU4VCHKycHBw1NTUrK+vGxkZcXBwjIyMmJmZCQsLg+wBCgoK165dS0lJYWdnFxAQmJ2dXVtb09HR4efnf/36NQ0NDcgy9fDhQygUGh4e/vr169OnT59MPXV8fAwQEK9evbq7u5uZmUlJSfnixYvx8XEREZHLly9vbW2FhYURExMD1bynp6eQkJChoSFQUqurqwsJCYWFhbW2tvLw8MjJyX358qW3txecc2NiYs6cOWNqaopCodLS0igoKEJDQ0FJABwWGhqKQqFSUlIQCMYhXFUAACAASURBVISTkxMKhcrJyaGgoHj37l1nZyc7OzshIWF2drabmxsPDw/wlQJDMD09raCgAIVCY2NjTUxMAHSql5cXAwPDs2fPgoKC8PHxFRUVb968qaurW1pa2t3dDbA44uLinj9/DoVCAwICZmZmwIV1YGDg4sWLUCi0ubk5NDSUkJBQX1+/vb19dna2vr4eAHN+/vyZm5ubnJx8YGAgMjLy9OnTLi4u4NYCWAIolerq6uBHfn5+MTExDQ0NLi6uW7duaWhoSEtLt7a2lpeX4+Pj8/DwIJHIiYmJtbW1y5cvU1BQ1NfXV1dXU1JSXrhwob293d7enoyM7NWrV3t7e69evSIlJS0tLX327BkuLi4JCYmOjg7ASygsLEQgEIaGhuB4x8/PDwLrAfX398vLy8NgsOfPnw8ODi4sLAA88dra2snJSQCkZWdnByDX7969i0QiATrK3t6ejY0NSPSBQqFiYmIA1uPAwICMjAw2NjYLC0tISAgKhZqammJjY7t58+bu7u74+DgfH5+xsfHe3t6HDx9Onz6tra1dU1OzsrLym4aiP0pw6+npMTExVVVVoVAoGxub8+fPR0REUFJS3rx5E4VCdXZ2cnFxOTo6dnV1SUlJiYuLT09Px8XF0dDQREdHBwUFUVFRAQATFxcXEhKSpKSkvb299PT0s2fPqqmpjYyMvH79mpycHAAPPXz4EB8fPysrC3wadHdxcTEcDr9y5crBwUFhYSEUCpWUlPz27Ru4dnl5eZ0/f15HR+f4+Dg9PZ2cnPzWrVuTk5OcnJwCAgITExP7+/uqqqqioqL3798nJyfX1NTs6+uzt7enoaHJysry8/MjISG5fv06yJV1eHi4uLjY0dHx8OFDOBweFRW1trZmb28PEPhevHjBxsYGYIIdHBxoaGjQTgsnRfa3b9+GhoaACltCQkJeXr6kpERUVJSUlPTp06cfP34E+uWCggIEAqGtrb20tOTh4QGQ8tPT06moqD58+LC0tDQ9PR0QEHD69GkHBweQfhs9KI2NjaSkpGpqakpKSlFRUZ6enqdPn7548eLbt28zMzMBYgM5ObmcnBw6FkNUVJSbm7uvr29jY0NZWfny5cvv3r1jZmaOi4tDoVDx8fFwODwzMxNt8yksLAQgfygUCqwoAwODrKwsZmZm4DVUWVkJh8MDAwPz8vIYGBjAjzU1NQBQTEtLC2SxGBsb4+XllZeXLywsvHTpEsiTgh7c/f19kKuhoqICgPFycXFVVVWlpKRQUlKGhYXNz88bGhpycXH19/fv7OwAjCd5eXlCQkJNTc3379+DrG+JiYlQKNTHx2dra8vBwQEkuLCzs2NjY+vo6FhdXb106RIdHV1JSUlsbCw5OTkzM/OpU6devXq1sLBgaGjIysra39+/uLgoJyfHyMg4NDQUEhJCRETk5uY2MTEB4LBPZr+tra0lIyO7fPny8PCwjIwMNzd3VVWViYmJkJBQenq6qakpFAq1srKKjo4GY52amkpOTn79+vXJycmbN2+ysrL29PQgkUgaGhpnZ+fs7GwYDCYvLw+2PUxMTLRDbXZ2NjMzs7m5eVBQEDY2tqam5sLCwrVr1/Dw8IALAKCDgwMfHx8CAoL379+jUKi0tDQSEhI3NzdRUVESEhJjY+P09HQA8w2AydApQMfHxzk4ODQ1NZeXl1+8eIGDg/PmzZve3l5OTk5ubu719fWpqamzZ8+KiIj09fUZGBgQEhJiYGDIyMgAqy/QcCYlJV27dg0XF/fJkydob5OdnZ3Nzc3k5GQ6OjpBQcGZmZmlpSUpKSk5ObnZ2dmoqCgiIiI+Pr7Ozk5/f38mJqYPHz44OztTUlKmpKQ0NjZSUVGxsbGBqWJgYEBFRVVbW4tEIvHw8DAxMfHx8cPDw4+Pj319fQkICMLDw1EolIeHBwkJCQA6Byo+YmLiyMjI3zfv/zmCu7u7m5mZWUtLa21tLScnh5OTMzAwsKSkBAKBGBgYpKamSkpKAl2bm5sbOzs70APa2tri4ODw8fEBtWl+fv6zZ88oKCjw8fH19fXv37/f1tbm4+PDzMycn59vZ2dHTk7u5+fn6+sLLnEnoTJRKJSvry8EAnn8+DEAk8PHx4+KigJ3TygUeubMGQAuGhMTA7RdmpqaRUVFxMTE8vLyU1NTIEeMt7e3jY0NBAIJDw9fWFiQkpLCwcFRVlYG51Bzc3MkEmlvb//u3btHjx55e3u3tLQAYNixsbEzZ86QkpLGx8cDrWt4ePizZ8+AMs7NzW1oaCg5OfmkidLS0lJcXBwYMElJSQMCAgYGBnh5eQHEYHJyspOT09jYmIODAykpaVZW1tevX6WlpQkICExMTCwtLfHw8C5cuODr6+vk5PT161dFRUUlJSUQUoiegh0dHRAIBAKB3L59e2lpCWCwGRsb5+fnP378ODQ0FFyrwTJGoVC9vb1AUb6zs/PmzRsxMbGqqqqIiAiQUufdu3cMDAwQCOTJkydoV/2QkBBsbGxpaemXL18ClFRRUVE5OTk8PLyHDx+GhYUBvbOtre2DBw94eHgqKiqmpqZMTU0VFRVBDjZRUdH09HSAGiouLv748WMRERFiYmI0PjAKhdrd3T137hwJCUlUVJSlpSWAhfPx8bG3twdZGYeHhxkZGZWUlIAxkIeHJyoqCuQ6MTExyc/Pf/XqVVJSkp+fHykpqa2trZWVFQkJCVCIwWAwISGhxMREKysrHBwcGAwWGBiop6dHSkrq7u7Oy8srIiKira2Nj48PNh6QL5GSkjInJweop3t7e9PT08nIyOBwOBq/dH19/cmTJ0REROHh4eHh4WBnTUtL4+bmJiIisrOzMzExgUKhbm5ucXFx7u7u9fX1JiYmtLS0ZWVlfX19AgICBAQEfn5+fn5+2NjYJ7W0FhYWREREqqqqwCdqe3vb3t6ekJBQVlaWlJQUAoHIysqWl5cDZN3r16+j0yt/+/bNyMiIkZGxrq6uvb2dm5tbSkoKwOqCJHMAVO/9+/cAvBDYS/b29p49e0ZISEhDQ5OTkwOysllZWQH49XPnzgGARpDDDCD6GhoaXrhwAWgOfX19JSUlEQjErVu38PDwACgx2uhdXl5uY2ODRCKDg4NPnToVGBiYkZFBTExMT0+PRCKNjIwICQlDQ0N7e3uVlJRAq9nZ2aFQqJmZWXh4OMBwz8rK8vDwICIigsPh4eHhLi4uCATC2NiYgYFBUVHRx8cHqJWsrKx6enp0dHQA8KyxsfHTp087OzvZ2NiuXr36+261f5TgvnDhAj8//9WrV3V0dDw9Pb99+zYwMCAoKEhMTHzz5k1paWmwgXt7e9+6dau5uXl7e/v69evExMS3bt26ceMGLi4uLy+vpqamqKiopKSkoqIiGxubkpKSkJAQcMsFYKc8PDwGBgbs7Ox0dHRv374FznZHR0eVlZXq6up0dHRWVlatra3W1taysrKjo6Nzc3NCQkIg+Za6ujpITAVOK1euXOno6LCwsAAqdRERkUePHg0NDTk6Oqqqqk5MTHz58kVfXx/cpquqqnR1dRkZGfX19S0sLMLDw+/fv8/MzAzsruXl5ZOTk2fPnuXh4SkqKgJJmCQkJO7evSsmJsbLywsSuUpISJx0a7WxsQFQ3RcuXLC1tf327dvS0hJIWiYsLHz16lUXF5eZmRlTU1MDA4OZmZn+/n5xcXEaGhpXV1d9fX1CQkI9PT0LCwseHh5ww3358iUwsqMFNxrqGizd6upqgAKqoaFx//59cB+XlZVFh+lPTk7q6upyc3Nra2vr6OiATEYgWw0dHZ2Ojg4HBwc7O/vbt2/Bh1AoVHNzs4SEBAQC0dbWvnr1KiYmpqam5uvXr5mYmIARX0BAAIwySDQhKyurqqp68+ZNAHoHUu3IyspqaGiAy4G3tzcHBwclJSXIfwTo6OjIy8sLBweHmZlZX1+fiooKgUC8f//e2tqagIDAzs4OZBoiJiZWVFTU0NB49+7d5uZmTk4OExMTNTW1srKyiYlJeXl5YWHhuXPn5OXlVVVVRUREzp49a2pqamRkBMzpurq6HBwc4uLi8fHxV65cuXHjxsDAgJmZ2alTpy5fvqyvr49AIAQEBNTU1Hh5edXV1VNTU2VkZKysrJaXl7OzswUFBZWVlUFiIxQKNTc35+TkBK5uXl5eoqKiwJdGRkZGQEAAQEKTk5Nzc3Nfu3btxYsX7e3tWlpaN27cACmnFRUVBQUFg4ODw8LCaGholJSU7ty5w8nJKSEhYWZmJiMjk5aWBjyIdnd3/f394XC4hobG3bt3mZmZ1dXVgeEBgUBYWFigpWRDQwMvLy8ODo6UlJSKioqysnJ5efnx8THIA8XFxaWqqurj4xMbG3vhwgV7e3vw1tbW1p07d7CwsERERAoLCw0MDCAQiLOzc0tLy4ULFyAQiKSkJEgDJiAg4O3tLSkpmZaWVlZWBofDYTCYra0tSNTAz88PoOGFhIRAChQUCuXh4QGBQLi5uZWVlYWFhQsLCwESFjU1dU1NjaysLEjWU1VVRUpKCoPB9PT0iImJIRCIo6Njfn4+MzMzBAI5c+aMqqoqAQEBERGRn5/f7du3ZWVle3t7L1++DKDtwfHFyMioqqoKMCMjI0NGRoaLi3v58mVOTs63b9/+fjzOnyO4d3d3a2trX716ZWNjA7Qc4MeSkpInT558+vSppaUlNDR0dHR0dHS0ra0NhFMjkcjo6GjgSO/n5/f06VOQibmsrKysrCw1NfXhw4cODg7V1dUoFAqoIHx9faurq/Py8lJTU9HT8ejoqKmpKSoqKjU1FWT6AJq4nZ2dg4ODxMTE6Ojo1dXV/v7+58+fV1RUTE9PBwYGAl9vcNY2NzePiora29s7Pj4uKysDWXLW19crKiry8/PBiLa1tbm5uQHtNkg47e/vb2Vl9enTJxQKtb29nZeXB2AqJycn/fz83rx509PT09TUVFpaOjs7W1tbGxoaevLEPTExER0d7ejoGBMTAwT60dHR8PBwUFCQvb19Tk4OKFxZWdnW1gYiDjIzM9PS0hYXFwsKCkJCQgYGBlpaWqKjoy0tLaOior5zSj0+Pl5dXa2trT2Z7bC8vNzBwcHX1xdElgIPtpMKlvb2dnd3dzMzs9zcXKAGnZmZef/+/ZMnTwoLC0tLS3Nzc09iXOzv7xcXF3t5edXU1ExOTgYEBAC9dnJyMkgiXlJSEh0d7ePjIyYmBsScs7MzOpdQV1fX06dP37x509TUFBsbW15ePj4+Hh4e/vHjx+88DmdmZgICAkBy+pSUlKioqKWlpYaGhrCwsG/fvh0cHIBcixYWFlFRUWBHX1hYyMjIePToUUBAAFDEra6ufvr0CWB/19fXFxUV7e7uLiwsBAQEhIaGtrS0FBYWFhcXLyws1NTU9PX1gS56+/btwMDA1NRUeHh4cnJyc3NzaWkp8PIsKChob2/f29ubn5/Pz88/iVSztbXV3t7e1NS0v7/f2dmJzkYPMo4fHh4uLCxEREQ8e/YsJycHvFJQUNDW1ra/vz87O1tQUFBZWbm2tjYyMpKQkFBZWbm1tQXm2NTUVFNT08kT4sTERExMTF1d3cbGRlZWVnV19d7eXnl5eWJiIjB7AIqMjMTDwzt//ryVlZW3tzfaJXFsbCwyMtLZ2Tk2NnZjYwMA2Q8PDwPN3v7+fnl5eWBgYENDw97eXl5eHvDCRKFQpaWlzs7Oz58/T0hIePr06adPn7q7uwsKCqanpw8PD+Pi4t68eTMyMlJZWenl5ZWRkVFYWOjt7Z2RkYG+K4MarK2tbW1tkUjk4eFhX1/f06dPU1NTd3Z2UlJS0tPTNzc3JyYm/P39Y2Nj+/v7Q0NDX716NT4+vry8HBsb6+zs7OLiUlJSEhkZ+e7du8HBwdLSUqBHLS8vf/Lkydu3b1+/fu3r61tTUzM/Px8XF+fr6ws8RB0dHc3NzYODg0Gs2W/SHyK4/27oxz946599AvX3QT/QH/pptMi/fet36j/6F/1X+Plb7/5XCv/Vd4Ej4C+C8b6jR48e4eDgAAeykzX8Jm//oPk/vvKf68NfR8r8hz6Kpn/bLlBgaWkJKDQiIiJ+v+ZfzNX/ekv/Z+r8Tfr96fHnCO7v3CS+C4pD/TAe6Ec/vvtXlf9VDf+28h/L/1Xlf1X+OwZ+2t6fPv2xtuP/k77rsb/i/0c+f6frfsr5r3//KSc/Pj3+gX58evKP9fX169ev4+DgoB1Fjk8AIv7Ygb/m9kf2ftE5v2jyyYD4vyr8V/X8tDd+fPpXHfJXDP/m0Bz/bIxO1vZj76FQqI6ODj09PTU1tdLS0t+s8Pj/xK38acn/j703j6eqa//HT5NkljHzmDEOIpFZ6JBUpsJR5jkzkSlzQlGZM2ZMxkSZiswVMidjhgZk5hj274/1evbrfFG3e3w+v577/UevnHP2Wmuvvda11r7Wdb3fW+56x176zW9/cu9bPsT+fHvP/OiqHR/Bj5r0m/hFDPd27L4L/sX/Aj5//vzo0SMHB4fi4uItX/07VP4BAKs0NDRUUVHR1NQE+xj/xR/DL2u419fXFxcXp6end68G9L+Jn5it5eXlXSbg/h/E5ubmj5gLgRFZXV2dmZmZnZ39L94jBoP59u0byJD+b7XhD2BtbW15eRmcx+zyks1tvqZdXru5ubm4uDgzM/P9+/f/ItXwX4W/ak79soYbKN25u7sXFRX9n33e21+mVlZW5ufnf9eU+DNYXV2tra19/fr19+/fsWsEYpKJiYl/Hw30ju+efx4YDAbcy9LSUmJiYlhYGLZyJoz19fXGxkZPT8/U1NQ/Q/26tra2uLiIwWC2t3/7DW7/TVtbm7Ozc2ho6Hamoc3NTWDWAd/0H27hX47Nzc2BgYGHDx9mZGTsMj8b2l1v7IilpSUQJRUXFzc1NbWwsLCdowb6D4fXwsLCbib73zHwfhOLi4tlZWX37t2DU///DH5Zw43BYDw8PEhISMLDw//Pbhvh4QsmPwRBDQ0N0dHR8FH7343R0VEdHR0CAgJsbsyNjY3k5GRKSsozZ878PEv+zwBetFZWVnbkwv9jaGtr8/LyAgxHoqKiBAQEgOd6CzY2Nh4+fEhKSuro6PhnDPfQ0FB0dHRBQcGOhhv6j2UHvEvbf5OWlkZBQaGuro69uqyuroIYuw8fPpibm5eUlPxf23nU1NQwMzODrKVdXgJ7dQEd4O6f9cLCgo+PDwkJiZGR0fv374ODg7fkIgB8//49Pj7+1q1bcLjRT1qCPen+McPd1tbGy8t78ODBn2gA7B6/rOFeXFy0t7cHnBX/7bb8Bubm5tzd3QHnSW5urqGhIcya/3ePqrW1NUNDQwQC4eHhAX/Y2trKzMzMxMTU2tr6d5uM0dHR+Pj4vLy8v6qi8vJyGRmZjo6O6elpOTk5MTGxHTc4a2trkZGRIF1txx3cLtHZ2amqqqqrq7vjt+vr6wUFBXfv3v3R+pebm0tOTm5rawvf/sePH2NjY9vb2zc3NxsbGyUkJGJiYrZQCv9e/LELf3JVVVUVJSWlnZ3d7jUKQGnv37/Pzc0FYZG7xPfv311cXAgJCcPCwt69eycpKamkpLT9mQ4PDwsICAgKCu7Sez42Nnb9+vWf0679tZifn+fk5CQkJKyurv7zpf0ihhvbg7a4uNjW1paRkSEtLS0iIgIioJeXl6urqz98+AB+Njw83NjYCKgjP336BIhVsUsDf7a2tra0tPT394Mw5I2Njf7+/vLyclggpqGhYWxsbGJioqura2lpaXV1dWxsbGpqCt5fdHZ2Njc3Dw8PT0xMLC8vT05OdnR0AILTurq6zc3NkZERR0dHEhKSqqoqCIIqKipevHgxOzsLGHsLCwurqqq+fPmytrbW1dX19u3bxcXFoaGh3t7etbW1Dx8+1NTUzM/PA2ZIQFkJQdDXr18rKys7Ojo+f/4MXPw/moSrq6tA9sHLywt80t/ff+7cOQQCoaWlBacDNDY2tra2gm1Of38/oOX79u1bTU0N9t4Hu5bFxUVAZ7iwsNDT07O0tNTT0zM8PIztzF1cXAwODgbEXlsaNjU1Be6osbGxrq4O3hQvLCyUlpaWlZUBEuTp6emxsTEMBjM2NjY0NLS2ttba2lpUVAR6mIODw8zMDPb2tLe3NzU1DQ4Ogkemo6NDT0/f0NDw6tWr/v7+zc3N5ubmwcFB7DGA7cWC+6elpaWlpQWE0tfV1aWnp/f398/OzlZVVY2Pj6+trdXV1X358mV9fR2omF+6dAnEdC8vLzc0NLx48WJkZAS0ysPDg5GRMTY2tre3t6Wlpa+v79q1a8zMzElJScvLy2/fvq2oqAAcre/fv8/Ly6usrJycnAT8dh8+fFhZWWlvb29ra1taWmpsbHz//v3a2tr8/Pzo6CgwqcCt8ezZs6dPn5aVlcG5V+B2JicnGxoaBgYGwLPo7u6Gn05TUxOsq/nx48eampqlpaWpqam6urqVlZXc3FwqKipAloudKDs9Pd3S0vLmzZuurq7tVN0dHR1nz54VFhauqKiAIGh+fr6kpKS8vBwMs+np6ffv34NcB7CJWV9fHxwcTEtLExcXZ2dn7+jo6OnpSUtLa2xs/Pr166dPn7BTvT5//hwdHd3S0gITnGE/vqWlpdHRUdixMz4+7u7ujo+P/+TJE/DJ6Ojox48fwf9hSwJzne/oWoE/hz/5/v37+/fvf8RNPzk5ycXFBcgztnyFHdoE7Q6/juEG91xTU6OrqysrKysoKEhKSurk5ARB0IcPH7S0tDQ1NVEo1IkTJ5qbm+/fv3/ixIng4GCQT2xgYLC9zJycHEVFRSEhoTNnzmRnZ29ubqampsrKysrJyWlqan769Mnd3Z2Dg+PcuXNycnI8PDweHh6+vr5IJNLa2hqUEBsbKycnp6SkdPLkyQsXLjx+/NjFxeX48eNmZmbKysrCwsIgy4OGhubAgQNZWVne3t58fHxBQUEzMzPh4eHi4uJnzpwRFRV9+vRpYWGhhISEjo6Oh4eHtLQ0Pz+/q6vrpUuXjh07lpubOzo6amVl5efnt7CwUFZWpqamBhYtFAoF1oMfDYja2lrAKGRmZobBYKanp69fv75nzx4iIqK4uLi1tTVAqSgvL49EIsPDw1+/fq2urq6goBAYGCghIcHPzx8WFpaSkqKiomJgYABSvdFodH5+/oMHD0RERIyNjS9evHjq1Km7d+9KSEig0eixsbFXr145ODi0tLSUlZVRUFAcOnTIz88Pu1UfP368dOmSgIDAqVOnTp48yc/P7+fnt7Gx0dHRcfXqVTk5OXFxcX9//+fPn1++fFleXt7CwuLEiRNOTk4pKSnHjx9/8ODB5uZmXl4eBQVFenr65ubmx48fr127pqampqyszMfHd/369ZGRERUVFRERESsrK0lJSUdHxytXrnBycrq5uc3MzERGRl6+fHnLtm5jY6OsrExeXh6QxD569KiqqoqHh+fy5cu1tbWA3UlLS0tVVZWDgwONRtfU1AA2Ozk5ue7u7omJCQsLCxERESQSKSgoaGlp+fXr13Pnzp0+fTo4OBiFQhkYGNy8eZOCgmLfvn0mJiZRUVESEhJWVlaAzF1JSQmJRDIwMAQHB7e1tfHx8YmJidnY2Bw7doyLiwuJRLKysp4/f76vrw8k5oWGhkIQVFRUpKioePHiRSYmJhYWFmAQARYWFry9vVlZWbW0tJqamh4+fCghIZGfn9/T02NhYaGhoYFEIk1MTNrb2wMCAri5uU1NTVEolIKCwvj4uImJyb59+5iZmdnZ2S9cuABYnLKzs+Xl5QGXlri4+LNnz7a4KP38/Pbt28fCwgICS1RVVSUlJbm5uQMCApqbm3V0dPj5+fX09JBI5O3btz99+mRgYCAvLy8uLk5AQKCiolJTU3Px4kUhIaFnz555e3sLCAhoa2tfvnzZzMzsxYsX4JcvXryArS1sf1+9eqWvry8lJXXq1Ck1NbWCggI3NzdKSkoEAvHgwYPV1dXMzMwTJ05wcnKePHkSjUYXFRW5urqKi4sLCwuLiIhg+y2Xl5fv3Llz4sSJK1eudHd3Z2dno1AowAJUWlp6+vRpDg6OU6dOVVZWVlZWnjx5UkVFxcrKCoVCFRYWPn/+nJWVlZSUlJ+f/+TJk7m5uRAEjY6O2tnZCQoKioiIyMvLwxlnv4lfxHADvHz5Ul5e/vLlyyUlJbq6uiQkJNnZ2R0dHSB1uKSkRENDg4iI6OXLl2FhYYAjwtjYmI+Pj4uLa3tp6urq5OTk6urq6urq4eHhsbGxEhISgYGB586dY2Bg6O7utra2RiAQdHR0kpKShISETExMIOdVVlZ2aWkpISFBUFDQ39//zp07JCQkQLbjwoULICsXML7q6endu3fv8OHDV65cGRoaAlS0169fn52dVVFR4eDgCAgIUFBQePPmTXl5OR4eHg4Ojra2trKyMuCl8/X1JScnv3PnzufPny0tLS9dulRUVIRCoTw8PIqLi48ePcrHx/dzd3lYWJi5uTk3NzcKhQJZlCdOnJCXl2dmZv706dPMzIyysrK1tXVAQAAODo6pqWlXV5eKigq4BQ0Njf379xsYGISFheHj4wsKCgI6LQYGhoaGhsjISMDUKiQkdPbsWT8/P1xcXD4+vrGxMRsbG1JS0hcvXjx58gQQMIFkP3h1WVhYEBQUBPnBDx8+5Ofnl5CQyMzMRKFQWlpa8fHxLCws58+fr6mpAQSkDAwMfHx8sbGxcXFxCATC399/ZmbG3Nycnp6+o6NjcXFRW1tbUlLy2bNnRkZGwC9UWVnJyckJ1vi7d++WlZWZmpoCUpF3797JyMgA4kbsvlpfX3dxcUEgECYmJoKCgsHBwdXV1Xv27BEVFR0cHHR3d0cgEHv27NHT0yMhIWFhYcnLywN0UdnZ2e/evdPX1xcUFIyNjbWxsdm7d6+5uTngDxATE1NVVdXT06upqYmOjiYgINDQ0Hjz5k1xcTEeXjPqpAAAIABJREFUHh4g9tLW1t67d6+VldXVq1cjIyObm5sJCQkRCIS8vPy5c+cOHDjg6empqanJxsZWXl7+4cMHFArl6+tbXV0tIiLi4+NTUlIiLi5OQ0MDc8cDX3NNTY2UlBQhIWFGRkZpaSkpKWl8fLyRkZGmpmZiYiJQb3nz5g3ICCcgIODj4zMyMhodHeXk5Dx69GhkZKSOjg4CgXj06NGrV694eXkNDAzS0tIYGBgICQmBtwe7A83NzREIxO3bt2tra+Xk5NTV1SMjI/fv36+hoTE4OCgiIoJAIBgZGXl4eCwtLa9duyYuLp6YmGhmZkZERBQaGjoyMsLOzo6Pj19bW2tiYoJAIA4dOsTAwKCvr19eXs7GxoaDg9PU1LRlm1xcXMzFxXXu3LmYmBg6Ojo8PLyMjAwPDw88PDxTU9PR0dHY2FgkEunk5OTv779v3z5BQUGwn+Dl5VVWVqaiogKkdQBra2tFRUUsLCxUVFTV1dX5+fmHDh26efNmTk6OvLy8k5OTrq4uIARtaGggIyNDIBC4uLiA6vLGjRsEBAQ6Ojq2trZ4eHi6urqvX7+2tLSUlpa+deuWrKzs3r17U1NTd+kz/KUM99WrV1lZWUF6OhqNFhISamlp8fb2BnSU4EMZGZmRkRFPT08EAmFhYfHkyRNpaWlAH7gFlpaW+/bts7CwaG9vz8nJkZCQEBAQcHBwOHnypL+///z8vIuLy8GDBz09Pb29vQkICK5cuXLnzh1KSkpnZ+eXL1/y8fEZGhrOzs42NjYeOXLk1q1b7e3t4uLieHh4vr6+KSkpNDQ09+7du3HjBgkJCXh5DAwMpKGhSU9PhyAIkFV6e3sDJ8yjR4+IiYlpaGjKy8vd3NwAq05NTQ07O7uPj8/g4KCWltbt27cvXLigpaUFPKqA3RiQIP9ox62iopKUlGRkZKSiogI0jiMiIi5fvqygoDA7OxsVFUVOTm5kZKSlpaWgoFBbW9ve3i4qKkpBQRESEpKcnExFRRUfH//ixQtGRkagOnTs2LHLly/PzMy4ubnh4eFZWVm9fv26p6enuLgY8GG+fPkSiURKS0t//fo1Li7uyJEjgPMPu5H9/f1AqaC7u3t9fV1TU1NUVNTd3R0XF1dDQ8PAwEBNTS0jI6O9vV1ERISSkjIkJASkX4eGhh45cqSurm5kZISDg0NFReXbt2+xsbEsLCyAFvXGjRtMTEy5ubleXl579uxhY2O7fPkyeON++PAhNTV1SkpKTk4OERERGo3eThwBiEwvXryYk5PT19dXWlrKysrq7OyMwWBcXFwOHDhw9uzZsrIyXl7eixcvFhQUnDx5UklJaWpqKi4ujo6O7tGjRysrKy4uLiQkJJWVlWlpaVRUVHh4eDIyMjU1NRAE3b17l5ycHBDIZWVlkZGRJSQkQBAUEhIC5nxtbe3k5GReXh4eHh43N3dJSYmxsTE3N/fY2Fh0dDQREVFhYeHTp09BCvXJkydPnTq1sLCAwWDExMQAA8mWO7p37x4ODo63t3dmZubp06fDwsLo6enV1NQuXLiARCKjo6OHhob09fWJiYltbW1ra2v7+/ufP39OQUEB1AwSEhLw8fGdnJzMzMxOnDgxNjY2Pj5+4sQJFAq1RUpxeXn58uXLDAwMeXl5YOuNQqG0tbVPnDiRkZHR3d0tKChIRER0+/btN2/eGBsbMzAwxMTEbGxsACUT4CdhZWU1MjL6/PkzINbX09MrLS3t7e0FryAyMjIwfQ0AeK86cuRIQ0PDzMyMtLS0gIBAV1fXtWvXKCkpgYuMk5Pz9OnT8/Pz9fX1R44ccXZ2Hh4ePnr0KDc3d1paWlVV1ZbIGQwG4+bmxsjIWFFRUVxcfPLkydevX6uqqgKxJCkpKRQK1dnZWV5eTk5Ozs7OHhkZ+fTpU7Ay0dPTNzY2Dg8PCwoKqqmpubq60tLS3rt3b2lpCWiJdHZ2/sS+YePXMdy1tbW0tLTXr1+HICgjI4OCguL69evv37/n4uICVLnt7e1sbGwWFha9vb2nT58+duxYR0dHdHT00aNHsWknASYmJt69e6eiosLAwFBXV/f06VNCQsIzZ87cuHEjOzt7dXX169evkpKSAgIC5eXlBgYGZGRkWVlZ4eHhDAwM2dnZjo6OZGRkgOnR2dmZnZ0dOA0BVVB3d7erq6uCgsLo6OilS5fExcW/fPkyOTl5+vTp8+fPd3V1AZ1yoH4wPDw8NzcnJiYG9pJdXV3S0tKqqqrfvn2rq6vj4uICC4mOjk5ubi49Pf3du3chCIqPj2dgYMjMzPxJj42MjCgrK1dWVrq5ubGwsEhISABieyYmJicnp5GRkePHj7Oyspqbm0dERIDNWlRU1J49e9Bo9PDwsKWl5fHjx0dHR9PS0lhZWUtLS+3t7ffu3fvw4cPBwUFBQUEJCQnYUkRHRwOFT3d3dzw8vIiICAiCrl69ys/PD84PsA13amoqERFRYGAgBEGVlZVsbGxgcSUnJ7eysgL6A+vr62FhYYcOHbKxsQEe8P7+fnl5eRUVFQiCCgoKSEhI7ty5A+hqNTU15+bmJicnJSUl1dTU6urqzp07h4eHh4uLe+bMGVCvo6MjoHbS1dXFwcHZIkG7sbHx/fv3gYEBXV1dAgICQHHl4eHBzs5eWVk5NDTEx8dHR0dXW1ubnZ195MiRrKys1NRUcnLy4ODg4eFhQFsGQdCnT5+OHz8uKSk5OTlpZmZGTEx88OBBcXFxsLHQ0dHh5uYG7zrm5uZIJLK/v7+9vb2vr8/KygoXFxdkiltbWwPW73fv3nFxcQH1rMDAwL179xoaGpqZmfn6+np7ewNyStCfxMTE8fHx2/3OiYmJCARCREQEjUYnJSWZmpri4+OfP3/+5s2bgKmqsrKSnJxcVFQUMGksLy/r6+vj4+ODYz1bW1tubu7z589LSEiAZwqIxR8+fIhNwA39R/UGjUYD/QpSUlJTU9OgoKCWlpalpaWIiIhDhw7p6+vPzc0NDQ0hkUiw5Lx+/ZqNjU1VVXVhYSEsLIyAgKCioqK5uZmJiYmXlxe4aCAIevLkyZEjR6Kjo2E/A6g3Pj6ekJAQyMLV1tbS09MbGBj09fXx8/MLCwuPj487OzsTEBAAX4ebmxstLW1GRsbMzExMTAwREZGSktKWlQAgJSXl8OHDhoaGioqK/v7+KSkpR44coaGhuXTpUnBwMGBQuX79OtjVgUtaW1spKSl1dHQWFxdbW1t5eHgA6y+4zZqaGkZGRlVV1d3rGv86hvvmzZsIBCIwMDAvL4+VlRWBQJibm4Odtaura1FRkby8PHgXjoqKOnbsmK+v79zcHBqNJiIigo/mAL58+WJhYVFbWwvYxXx8fB4/fgwUo0tLS8GmBtCfe3l5paenMzAwGBoaNjQ0KCoqEhERGRsbg5esysrK8PDww4cPk5OTP3361MrK6tChQwUFBV1dXXR0dJycnD4+PnR0dIDPLy0tjZycnJOTMzExMSEhoby8HGisREVFPXv2DCjp9PT0REdH4+LisrGxvX79+tOnT0DfAOzF4uPjSUhIPD09CwoKAIXs/fv3Ozs7a2pqdhQkDQkJOXfuXE9PD2CRBZTNHh4ehw4dAn5zCgqKI0eOJCQkvH79uri4uKenx8TEBB8fv7S0tKuri4qKCqh+GBkZMTMzGxoaUlNTIxCIoKCgkJCQI0eOwL06MTEB3C8WFhY8PDwIBMLNza2srAyJRFJRUcHkIfAkt7CwICUlbWpqGhsbk5GRQSKRkZGRp0+fpqKiSkpKevbsWWJi4tDQkIyMDDExMeAch/5jrEVERF68eOHh4YGDg6OlpZWfnw+UUKqqquzt7fft26eurp6WlsbBwSElJXXp0iVqauqQkJAHDx4wMTGdOHHizJkzBw8e3L9/v7u7OzaD0vz8vI+PD1BH4uTkVFNTa21tvXTp0qFDhwICAgoLC3FwcK5cuTI7OwsIV0NCQgAph6WlZVRU1OHDh/n5+R8/fmxsbHzo0CEkEtnR0SEpKSkvL6+trc3MzGxgYAAEjikoKDIyMoaGhri5uenp6aOjo8+ePZuSkvLs2TMiIiJra+ve3l5ubm4FBYXp6em4uLi9e/cqKytPTk4GBgbi4uKSk5PfvHmzu7vbyckJ6D6np6czMzMDWZ/trKEFBQV4eHgHDx708vL68uULGo1GIBCOjo6tra0JCQldXV2hoaEIBAKW1Ont7SUkJGRkZBwbG6utrZWUlAwMDAQrkJ+fX0FBATc39759+5ydnWHJY3Chh4cHAoFQVFSMjIzk4OCgo6PLzc2tqam5f//+ly9ftLW1iYmJwf4pKSlp37594uLi6enpYM7KyMg0NjYCFkDgydm/f7+XlxcoHMxWXFxcNBoN21nwFXB/3bhxA7jUEQjE2bNns7OzycjIGBkZq6urxcTEyMjIHj9+nJuby8rKSktLa2xsfPPmzerqagkJCQQCAdjKtqCoqAiBQBw8eFBdXb2rq0tDQwOBQEhISACPU2VlZWlpKZArA4cKi4uLDg4OBAQEz58/X19fNzQ0lJGRsba2pqen19LS6urqAuEACgoKvxnLCOPXMdzFxcVgoTY1NZWTk2NhYdHV1QXnKoKCghoaGlxcXFRUVK6urr6+vtra2lVVVcvLy3p6evv377969Sp2Uc3NzUCRElCzZmVlvX37FolE8vPzGxoaqqmpRUZGOjg4cHNzV1ZWJiUlIZHIJ0+eADPKxMRkb2/v6+tLRUWlpKQkJyd35MgRCgqK8PBwIOI3PT1dVlZGTEwsJCRkampKTk4ONumxsbE8PDx8fHyOjo4XL17U0NAAN1JZWXn//n2gyDM/Px8TE8PExCQgIFBRUbGxsXHlyhUyMrL8/HwIgrKzsykpKU+ePKmpqXns2DEaGhpAyIlGo+vq6rBvcGNj4927d0pKSnx8fK2trWFhYdLS0s+ePQMklkxMTFFRUdPT0xYWFjQ0NFpaWmg02svLq6amxtjY+PLlywsLC83NzczMzPz8/BEREWZmZoAYVlJSkpaW1tHRESgNwZUCRnI8PLwzZ84oKysDiuTw8HAhISFGRkag5wL9Z7ItLi6KiooeOHDA0tLSyspKQUEhLy9vYWHBzc2NhoZGXV3dysrK0NDw9evX4FnDnGo5OTlAXCotLc3T05OGhkZVVbWhoQHIpmhqasrIyBw+fPjq1ashISH8/PxRUVG5ubmMjIx8fHzW1tY8PDycnJx6enqioqJEREQ2NjbYyUfT09PCwsJIJNLZ2VlUVPTOnTuAfvbQoUPm5uZ3797l4uJ68eIF0JwkIiJydnZGIpEIBAKNRqempl64cIGamlpOTk5WVpaSkpKfn//p06eSkpIhISHl5eUSEhIcHBxycnJAY9PDw+PDhw+0tLS0tLRBQUECAgLHjx83NjaWlJRMS0urrKwUFBQE2QnAvSMgIDA+Pp6dnU1ERCQtLQ20nuPj4+no6NTU1NBoNAsLCzU1taOj4/Z0qubmZkVFRU1NzYGBAaDqycbGdurUKR0dHS0trfr6+oCAACEhIRBHBEHQyMiIuLg4CwuLra2tlpaWm5vb9PR0VlYWExMTOF6ip6cHoovgNQg23J6enkRERDIyMgkJCdeuXaOmpj5z5sylS5e0tbUHBwfPnj2rqqoKWv7q1StJSUkaGholJSUpKSnAdl1ZWSkpKUlMTHz+/HlRUVGwPIOSBwcHwYmRlJTUFsMXHBxMTEx8/Pjxq1evgtNIXV1d8NZIQkJSUlJiaGi4Z88e4NsBCzbYfIiKirKwsAgKCu4YuQicRfLy8v39/RsbG0AWh5mZWUtLS01N7f79+6mpqXx8fDo6OuAVZ25uztLSEgcH59q1aw4ODgICAmlpabW1taysrEDjAh8fH4FASEpK/i8a7uXl5ZycHDc3t4aGhk+fPqWlpdXX129sbDx69MjExCQ2Nvbp06cPHjzo6+tramoqKysD+srJycnXr1//+PEjthcYEFQ6Ojpqa2tHRETMzMwsLy9nZmbq6uo6OztXVlYC9u3k5OQvX750dnbm5OQAaaWMjIysrCwQ5Ofu7u7g4FBRUZGUlPTgwYOmpqbs7GwQVN7T0xMYGFhZWbmyshIVFZWSkrK0tNTf3//gwYNXr161trYmJycbGBioq6sD1+fbt29jY2NBjkZPT09UVBRwwtTW1l68eDEwMBAc34+MjPj4+Nja2mZkZDx+/Dg+Ph5si+7duwdCvmCsr68/ffr09u3bN2/e7Ovr6+vr6+rqmpiYSE9PDwgICAgIiI6OBoGSAQEBZmZmcXFxs7OzS0tLhYWFIJ9lbGwsLi6uqKhobW2tvLz8zp07AwMDnZ2dd+/era+vB/o4cPTxwsJCUlKSpaVlX19fW1vb3bt3QTRbVFRURkYGCFyDz2R6enrAsaqcnJytrS0QloQgqKury9PT88qVK8nJybOzs1NTUw8fPoRP2yAIamlp8ff3r62thSCovLwcPGsIgioqKszMzMLDwwsLC4G2xtu3bxMSEsbHx4eHhyMjI5OSklZXVwsKCkJDQwcHB2tra4OCgrak7aysrMTFxdnb2yspKbm7u09OTm5sbERHR/v4+Hz48OHly5cJCQnfv39fXV2Nj48PCgoaGBiIjo42NzcHe67q6mpfX9+kpKT29vaoqKiSkpK2traEhIS2trbp6ens7OzMzMzm5ua0tLTk5OSZmZnp6el79+6lpqaurKzk5+fb2dmZmZklJSUtLCz09vY+evTow4cPIOYnJibm9evXYLwpKCjATr+BgYHIyMi7d+8+ffq0oKAgOjp6x1jykZGR4uJimJka7OLRaPTNmzeBla+oqHjy5AlImdnc3ATBjubm5hcuXAgJCQFb+PHx8aysrNu3b2dlZeXk5ERFRbW1tcGXgJLr6uoCAwPBWU5XV5eTk5OysvLdu3cXFxeBdHJhYSEIXQURn97e3llZWUB0pqCgYGFhISEhITAwEChrp6WlwcLwCwsLWVlZdnZ2LS0tW+JYPn78GBgYqKure+fOnaioKFNT07a2tjdv3qDRaFB1U1OTgYGBhoZGZGSkt7e3gYGBl5fX2bNnFRUVz58/n5eXtz3TBwxRIGYL/vz8+XNYWNjZs2dRKFRcXNzKysrY2FhSUhII6IL+k6Z77do1OTk5ZWXl9PR0DAYzPz8fHh4ODv89PDy0tbXT09N3rG5H/CKG+8+nGPyc4XM35e+yDX+Y5RX7/93d3SUlJTo6OjDT/F+eKfOjVMAdv/pRCZu7o12Fg7eAKxMXFxfoJ+ymMdv//NH/fy+wW/6bDfi9H/55gGKBQxYcbWGr0/3kkh3xc5rfzf+XSXHLhT+55C+cOD+q4kdf/a3d/rtq+TuGyi9uuH/eEbt8Btu/+jNj4kfB/L/rWkdHR0ZGRgMDA+yEkT/cpJ/XBf+5Y2t/vtrB2GVdHz580NTUpKamzsrK2rHqnzTvN/+/mwbspsw/U87vveQ3B15dXR03Nzc3N3dsbOzPk61+86s/9ih3P2t2/P0uJ9ePPvz5tN3x893/4Ec1/ujP3Re7y875CX4Rw/2/hp6ensbGRuAR+5t2Fv88NjY2RkdHi4uLc3JyOjs7/0wm+v8CwHNfWFh4+vRpe3v7/7/4Bf/Fn8S/hvuvBKC7/NG3m5ubv4te50eFYL8e/uZ+9ievk38Sf/nb6Obm5tra2tra2vr6+tra2u9t9urq6s+N18bGxs/pxsAd/abTbPe6OX8HNjY2QBfBT/YPP18MBrM9QHBLXf/AzcIaN395RX9+uv2fxa9muH+v8+E3S4NHFfZhCzzD19fX4QE3MzMTGxvr6uqKnViMjffv36elpf1jzH8A4+PjxcXFjY2Nu/RawMC+0+3fYjAY4GcfHh7ezrP8V9l0sNRtOeYC/8fueQiCenp6bt++HRcX9yOd7P7+/qKiouLi4v7+/h8R1H3//r26uvrp06fYGonYjfny5cuLFy+AIOSfvK8/dsnKygoIoQNqpb95yfr6OgaD2dGy9/b2hoSEwG7xHdHW1paWlgZOgP/ydRpgfX29tbW1sLCwurp695RVv4nNzc2mpqa0tDRsBc7dXAUPqt1r++0S26fJ9vKXlpaA4uhvdsWvZrhh/FWGA4KgkZGRmJgYbK8rBEHr6+vFxcWZmZkgRHpyctLDw4OHh+fo0aP6+vo7PvKwsDAqKipAn/KPoaam5uTJk+fPn9+Rlno32LEn5+fnQ0NDjx07lpOTs2Ub+xfunjAYTFJSUkxMzJb3mOHhYT8/P6CnDEFQYWGhhoYGJycnCoWCA9ewUVtbq6mpefr0aV1dXRD7BcIbtmBsbOzixYsnTpzAznLGxqtXr0RFRVEoFBzr8o9h8z+xki4uLvT09CC78jfx+vVrPz+/Hdeh4OBgwJX6k8tjYmKoqKhcXFyw2/DXYm1tLT4+nouLy9LS8g8P0e0YHx/X0NCgoqICGbO7xG/6r/8wFhcX4+Li3r17h13m8vJya2srLFo9ODhobGxMQ0NDQ0PzmwyCv4jhhnt5fX29pqZmx9n7h9HZ2Xn27Fk0Gg1BUF9fX0REBKCmMzU1vXjxIshS9fHxERQUTEhIqK2tBYQJ2zee169fx8HBCQoK+qsatpuB9fz5c35+fmNjYzjS6CfnPNg/WF1dzcjI+NHWEmT8k5OTd3d3wx92dXXV19dvj0Xd5QTY/rOZmRk0Gn3hwoXp6enFxcXnz5+Xlpaur6+/fv2anp4eJDd2dXUpKiqamJi8fPmyubl5enp6e1PV1NQUFRWBGrquri4VFdWOiRXj4+PCwsJSUlLYmvTYKC0tJScn19PTg9Ogt0z17Xf0o97OzMx8+fLlbsK/sEtYWVkxMDCgo6PbEpj/I5SUlGhrazc0NGxvhp2dHcjF/cnlsbGxIAP5563aJXbsDcCvi4ODc+vWre1+m59370+wuroKsuFg9foda9+xzOHh4dLS0u2PZpeX74j6+npWVtarV69+/fp1eHi4rq5ubm5uamrKwsJCTk5uYmJifn7e0dFRSEgoPj6+uLj4NxXffx3DDf6NiIg4ffp0Xl4eBEGwbNXk5CQ8Jnp6erADWtfW1oChWVhYAPyZEAR9+fLl7du3TU1NwGwNDw/HxMRUVFR8/PjR1NSUk5MTWIeUlJTCwsLh4eGioiJGRkY1NbUtTYL33QMDA62trRcvXuTn5wcBwuvr601NTc3NzR0dHYA4v6urC+QsTE5O7pj5urKyMjExAY7spqen4ZeppaWllpYWuPGA8RXcEQRBUVFRnJycISEh25WfQOw23FrsUbiwsODn58fFxQXvar9//97X1weP5rGxMVNTU1lZWVh86+vXr9bW1q6urj9KIlhZWRkdHQXx4KDZ4EEsLy/DccSgVXBLJiYmioqKXr16tbq6mp2dLSoqGhsbC0HQ+Ph4RkbGhw8fAC0iAwNDamrqjpVCEDQ1NcXDw8PIyAiC33Nzc62treEbaW9vn52dBcS5T548ISYmdnJygl+WBwYGxsbGlpeXl5eXNzY2njx5cvjwYRCq+PnzZ5hBFO5DCIJWV1fb29sbGhrgLD4MBtPV1dXQ0NDW1gaG4qNHj7i4uIKCgr5///7x40cQkjw/P7/jmgeKnZ+f7+zsfP78OQqFUlVVBVXPz8+3tbV9//798+fPGAxmZmYGqKB9+/Ztbm4OUEUWFhaC8rGxuLioo6Nz9OjRgoKC5uZm2J8wPDyM7cq7fv06HR0dIM8BAAS/8AOFXzfBZnl1dRVe0lZXV1dXV1dWVjo7O7ck7o6Pj7958wa0anFx0cTEhJmZubKycnR0dGBgYMtBxcbGBkzTiMFgFhcXwb0vLy+3tbWNjo6CrxYWFkCB375929zc7Ojo4OfnR6FQMB0x/JiWl5ex27PF+L59+/b8+fNwUtiWZ7H9w11icXHxxYsXgGrGyMjI3Nwc2JbW1tbnz58vLCzk5eUxMTFtSeH+CX4Rww1QVVXFycmJQCAiIiLy8/MvX77s7+9/7do1XV1dIFvn7e2NRqPV1dV1dXWrq6tbWlq0tLTc3d2fPXumrKx8+fLllpaW4uJiU1NTVVVVQCDZ1NSkpqbm4ODQ3d0dGxuLh4dHTk5eXV198+ZNVVXV3t7e7u5uRUVFkCO33TO1vr5++/ZtNBqtra1NQkKira0Nc6WqqKhISUmdO3fu06dP/v7+0tLSSUlJvr6+SkpKt2/f3iLLMjc3p6Ojo6SkBOjfrKyswsLCvn379vjxY1NTUy0tLWNj487OzkePHikrK/v5+ZmYmJiamvb19Xl6eu7Zs4eRkVFWVtbFxQUMl66uruvXr+vr66urq+vp6QHJbWwDVF1dDfhFHz9+DEFQdXW1jo7OhQsX0Gh0QEDA1NRUQ0ODgICAi4sLIKWKjIy0t7cnJiY+ceKEl5eXhYVFeHh4UlKSra1tX1/f5uZmUlKSnp4e6AcHB4eUlBQbGxtXV9eMjAzAtlpZWTk/P+/n56epqampqRkSEtLR0REQEKCvrw/yg7i4uBAIhJ2dXUlJibm5eWhoaGdnp5ubGwkJCRKJBJlKO2J1ddXe3h6kO/f29s7MzADm5ZcvX1pYWOjr62toaGhoaAwPD1+/fp2AgCAxMRGCoLGxMTc3N1VVVX19/UuXLoWGhoLxIyQk5O7ubmJicunSJZDsg42enh5zc3NdXV1xcfHw8PCNjY3x8fEbN26oqalpaGjIycmBxA0BAQEEAmFgYODg4CAnJxcYGDg+Ph4TE2NsbIy9hsF4+fLllStXVFRUJCQk6OjowPSuqKg4d+6cnp6eurq6hoZGdXW1h4eHvr6